Composite, manufacturing method thereof, and shape memory member including same

A composite of crosslinked polymer and metal nanowires enables electrically driven shape memory functionality, addressing the issue of environmental heating in existing shape memory materials and enhancing control and safety in tissue interaction.

JP7602220B2Active Publication Date: 2024-12-18NAT INST FOR MATERIALS SCI +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023520957
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-08
Filing Date
2022-04-26
Publication Date
2024-12-18
Estimated Expiration
2042-04-26

AI Technical Summary

Technical Problem

Existing shape memory materials based on aliphatic polyester resins like polycaprolactone require heating of the membrane and surrounding environment for shape recovery, which can have adverse effects on surrounding tissues.

Method used

A composite comprising a crosslinked polymer and metal nanowires, such as silver nanowires, that can be driven by localized heating through the application of an electric current, allowing for shape memory functionality without the need for environmental heating.

Benefits of technology

The composite achieves localized heating and shape recovery through electric current application, reducing potential tissue damage and providing a more controlled and efficient shape memory response.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602220000023
    Figure 0007602220000023
  • Figure 0007602220000024
    Figure 0007602220000024
  • Figure 0007602220000025
    Figure 0007602220000025
Patent Text Reader

Abstract

The present invention provides a complex which can be used for a shape memory member that can be driven by local heating by means of the application of an electric current. A complex according to one embodiment of the present invention comprises: a crosslinked polymer that has an endothermic peak when the crosslinked polymer is subjected to differential scanning calorimetry (DSC); and a metal nanowire. The complex has electroconductivity at such a level that the electrical resistance of the complex can be measured in an electroconductivity test in at least a state where the complex is not deformed and a state where the complex is deformed at a scale of 100% or more by applying a stress to the complex in a specific direction from the outside of the complex, and the detachment of the metal nanowire does not substantially occur in a stability test using a good solvent for the crosslinked polymer and / or the metal nanowire.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite, a method for producing the same, and a shape memory component including the same. [Background technology]

[0002] Aliphatic polyester resins such as polycaprolactone are known to have excellent biodegradability, and research into them is ongoing. Non-Patent Document 1 describes a temperature-responsive poly(ε-caprolactone) membrane. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] K. Uto, et al., J. Control. Release, 2006, 110(2), 408-413. Summary of the Invention [Problem to be solved by the invention]

[0004] The membrane described in Non-Patent Document 1 had a shape memory ability, that is, it remembers the deformation applied and returns to the shape before the deformation was applied when heated to a certain temperature (hereinafter, this temperature is also referred to as the "driving temperature"). However, in order to exert the shape memory ability, it is necessary to heat the membrane and / or the surrounding environment of the membrane. For example, when applying to a living body, there is room for improvement in terms of the difficulty of selecting a heating method and the adverse effects of heating on the surrounding tissues.

[0005] Therefore, an object of the present invention is to provide a composite that can be applied to a shape-memory member that can be driven by localized heating caused by application of electric current. Another object of the present invention is to provide a method for producing such a composite, and a shape-memory member containing the composite. [Means for solving the problem]

[0006] As a result of extensive investigations aimed at achieving the above object, the present inventors have found that the above object can be achieved by the following configuration.

[0007] [1] A composite comprising a crosslinked polymer having an endothermic peak when subjected to differential scanning calorimetry (DSC) and a metal nanowire, the composite having a conductivity that allows measurement of electrical resistance at least before deformation and when deformed 100% or more in a specified direction by applying external stress in a conductivity test, and the composite showing substantially no detachment of the metal nanowire in a stability test using a good solvent for the crosslinked polymer and / or the metal nanowire. [2] The composite according to [1], wherein the crosslinked polymer is selected from the group consisting of a cured product of a curable compound 1 represented by the formula 1 described below, a cured product of a curable compound 2 represented by the formula 2 described below, and a cured product of a composite of a curable compound composed of the curable compound 1 and the curable compound 2 described above. [3] The composite according to [1] or [2], wherein the metal nanowire is a silver nanowire. [4] The composite according to any one of [1] to [3], wherein the content of the metal nanowires calculated by thermogravimetry (TG) is 10% or more and 25% or less. [5] A shape-memory member comprising the composite according to any one of [1] to [4]. [6] A method for producing a composite described in any one of [1] to [4], comprising the steps of: preparing a molded body containing metal nanowires; applying a composition containing a curable compound to the molded body; and applying energy to the molded body to which the composition has been applied, to cure the curable compound. [7] The method according to [6], wherein the energy is applied by heating the molded body. [8] The method according to [6] or [7], wherein the energy is applied under pressurized conditions. [9] The method according to any one of [6] to [8], wherein the curable compound is selected from the group consisting of a curable compound 1 represented by the formula 1 described below, a curable compound 2 represented by the formula 2 described below, and a composite of the curable compound composed of the curable compound 1 and the curable compound 2. Effect of the Invention

[0008] According to the present invention, a composite can be provided that can be applied to a shape-memory member that can be driven by local heating caused by application of electric current. The present invention also provides a method for producing such a composite, and a shape-memory member containing the composite. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic perspective view showing a structure of a composite according to one embodiment of the present invention. [Diagram 2] 1A and 1B are SEM images of the silver nanowires synthesized in Example 2-1 and Example 2-2, respectively. [Diagram 3] 1 shows SEM images of the composite prepared in Example 3-1, (a) surface and (b) cross section. [Figure 4] 1 is a graph showing the relationship between power (W) and temperature (° C.) for the composite produced in Example 3-1. [Diagram 5] FIG. 13(a) to (f) are SEM images of the surfaces of the three types of composites prepared in Example 3-4 in a permanent shape (before deformation) and a temporary shape (after deformation). [Figure 6] FIG. 1 shows DSC curves of composite 4(10), composite 4(20), composite 4(30), and composite 4(50) prepared in Example 4-1. [Figure 7] FIG. 1 shows TG curves of complex 4(10), complex 4(20), complex 4(30), and complex 4(50). [Figure 8]Figure 1 shows the stress (MPa) induced in the specimens as a function of test time (s) after 20 deformation and recovery cycles: (a) Composite 4 (10), (b) Composite 4 (20), (c) Composite 4 (30), and (d) Composite 4 (50). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described in detail. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0011] (Definition of terms) As used herein, the term "permanent shape" refers to a state in which internal (residual) stresses in a given substance are relaxed, in other words, the most thermodynamically stable shape, and typically refers to the shape obtained when a substance is heated to near (or above) the melting temperature of the crystal in the absence of external stress, and then cooled to room temperature. The melting temperature of the crystal means the peak top temperature of the endothermic peak during the heating process when the target substance is subjected to differential scanning calorimetry (DSC) (when there are multiple endothermic peaks, the peak top temperature of the highest temperature peak is used). The vicinity of the melting temperature means about the terminal temperature on the higher end side of the endothermic peak in the differential scanning calorimetry. The differential scanning calorimetry is performed by the method described below.

[0012] In this specification, the term "temporary shape" refers to the shape of a target substance when it is deformed by applying an external stress, heated to near the melting temperature of the crystal, and then cooled to about the crystallization temperature (or lower), causing the deformation to be temporarily fixed by crystallization, etc. The crystallization temperature refers to the temperature at the top of the exothermic peak during the cooling process when differential scanning calorimetry is performed on the target substance.

[0013] In this specification, the terms "driving," "driving," "drive," and "capable of being driven" used in relation to the shape memory ability of a composite are intended to mean exerting the shape memory ability of the composite (that the shape memory ability is exerted), that the composite exerts its shape memory ability, that the shape memory ability of the composite is caused to exert, and that the composite is capable of exerting its shape memory ability (that the shape memory ability of the composite is capable of being caused to exert).

[0014] [Complex] FIG. 1 is a schematic perspective view showing the structure of a composite according to one embodiment of the present invention. As shown in Fig. 1, a composite according to one embodiment of the present invention (hereinafter also referred to as "composite of this embodiment") 100 is a composite including a crosslinked polymer 110 and a metal nanowire 120. Note that Fig. 1 shows an embodiment in which the outer shape of composite 100 of this embodiment is a sheet shape (which may also be referred to as a film shape, membrane shape, etc.), but the outer shape of composite 100 is not particularly limited and may be appropriately determined depending on the application.

[0015] In the composite 100 of this embodiment, the metal nanowires 120 are incorporated into the crosslinked polymer 110. In other words, in the composite 100, the metal nanowires 120 do not simply cover part of the surface of the crosslinked polymer 110, but are embedded inside the crosslinked structure of the crosslinked polymer 110. Due to this structure, the composite 100 does not substantially cause detachment of the metal nanowires 120 in a stability test described later.

[0016] In the composite 100 of this embodiment, the metal nanowires 120 are incorporated in the crosslinked polymer 110 in a dispersed state to such an extent that the composite 100 can be driven by localized heating caused by application of electric current. With such a structure, the composite 100 has a certain electrical conductivity. More specifically, the composite 100 has electrical conductivity to such an extent that electrical resistance can be measured at least in a state before deformation (permanent shape) and in a state in which the composite 100 is deformed by 100% or more in a predetermined direction by applying external stress (temporary shape) in a conductivity test described later. More preferably, the composite 100 has electrical conductivity to such an extent that electrical resistance can be measured even in a state in which the composite 100 is deformed by 100% or more and restored to a size similar to that before deformation by applying energy. As a result, the composite 100 can be driven by localized heating caused by application of electric current, and in a more preferred embodiment, the composite 100 can be repeatedly deformed and restored multiple times.

[0017] With regard to the temporary shape in the electrical conductivity test, the state of being deformed by 100% or more may be 100% deformation, 200% deformation, 300% deformation, or deformation exceeding 300%. It is desirable that the composite 100 has electrical conductivity at a level that allows measurement of electrical resistance in a state of being deformed by a higher percentage, and further has electrical conductivity at a level that allows measurement of electrical resistance even in a state where energy is applied in the deformed state and the composite is restored to the same size as before deformation, since this allows the composite 100 to be applied to a wider range of applications.

[0018] Furthermore, in the composite 100 of this embodiment, the metal nanowires 120 are incorporated into the crosslinked polymer 110 without substantially impairing the properties that the crosslinked polymer 110 has by itself. Specifically, in the DSC curves of at least two or more samples of the composite 100 produced under conditions with different contents (contents) of the metal nanowires 120, endothermic peaks and exothermic peaks are confirmed in substantially the same temperature range. This means that in the composite 100, the metal nanowires 120 are embedded inside the crosslinked structure of the crosslinked polymer 110, and that the amount of the metal nanowires 120 thus incorporated into the crosslinked polymer 110 does not substantially affect the melting point or crystallization temperature of the crosslinked polymer 110 contained in the composite 100. As a result, composite 100 can more effectively exhibit shape memory ability (described in detail below) due to the inclusion of crosslinked polymer 110, and can be driven by localized heating through the application of electric current due to the inclusion of metal nanowire 120, thereby having a structure that additively or synergistically combines the advantages of crosslinked polymer 110 and metal nanowire 120.

[0019] In addition, in the composite 100 of this embodiment, the metal nanowire 120 is incorporated into the crosslinked polymer 110 without substantially impairing the properties that the crosslinked polymer 110 has by itself, which also means that the metal nanowire 120 is incorporated into the crosslinked polymer 110 without substantially impairing the properties that the metal nanowire 120 has by itself. In other words, the metal nanowire 120 is embedded inside the crosslinked structure of the crosslinked polymer 110, and not only does it provide the composite 100 with the characteristic that it can be driven by local heating due to application of a current, but it can also exhibit the properties that the metal nanowire 120 has by itself when incorporated into the crosslinked polymer 110. Specifically, for example, in an embodiment in which the metal nanowire 120 is a silver nanowire, the composite 100 can exhibit antibacterial properties derived from the silver that constitutes the nanowire. Thus, in the composite 100 of this embodiment, in addition to selecting a metal as the material for the metal nanowire 120 from the standpoint of electrical conductivity (i.e., from the standpoint of enabling actuation by localized heating through application of current), as described below, it is also possible to select the metal from the standpoint of imparting desired properties to the composite 100.

[0020] The dispersion state of the metal nanowires 120 in the composite 100 described above can also be explained using the concept of percolation. The concept of percolation (percolation problem) is well known in the art, and its relationship with self-similarity is also well known. Given an n-dimensional lattice (e.g., a cubic lattice), consider the procedure of occupying the sites (or bonds) with a certain probability p. If p≒1, all the sites will be connected and a network of the entire lattice will be formed. On the other hand, if p≒0, there will be few occupied sites, and even if there are occupied sites, the surroundings will remain empty. In this way, the process in which points or bonds in space are stochastically occupied is called percolation, and a collection of occupied sites that are connected to each other is called a cluster. This can be considered as an idealized model of the process in which a liquid permeates through a random medium or the process in which a forest fire propagates.

[0021] In the percolation problem, p>p c The critical probability (percolation threshold) p for the first time that a cluster of infinitely large connected bonds (or sites) (percolation cluster) appears. c exists, and its value depends on the spatial dimension, whether it occupies a bond or a site, the type of lattice, etc. In fact, computer simulations have shown that percolation clusters have self-similarity, and their fractal dimension D is D = 91 / 48 = approximately 1.89 in two dimensions and D = approximately 2.53 in three dimensions. The value of the fractal dimension D can be calculated from a scanning electron microscope (SEM) image of the object.

[0022] In view of the above, in the composite 100 of this embodiment, it is preferable that the metal nanowire 120 has self-similarity based on the percolation cluster model described above or a self-similarity equivalent thereto. This makes the composite 100 excellent in electrical conductivity and suitable for use as a shape-memory member that can be driven by localized heating caused by application of electric current.

[0023] [Crosslinked polymer] The crosslinked polymer 110 contained in the composite 100 of this embodiment is a chemically crosslinked polymer compound. That is, the crosslinked polymer 110 is a polymer compound having a crosslinked structure in which molecules are bonded to each other by covalent bonds formed by a chemical reaction.

[0024] The method for introducing a crosslinked structure into a polymer compound is not particularly limited, but examples thereof include a method in which energy is applied (typically, heating) to a curable compound (crosslinkable monomer) described below to cause curing.

[0025] The crosslinked polymer 110 has an endothermic peak when differential scanning calorimetry (DSC) is performed. That is, the crosslinked polymer 110 has a degree of crystallinity such that an endothermic peak due to melting is detected when differential scanning calorimetry is performed, in other words, a melting peak is detected. This allows the composite 100 to exhibit a shape memory ability, in which the composite 100 remembers the deformation applied thereto and returns to the shape before the deformation is applied thereto when heated to a driving temperature.

[0026] Here, the differential scanning calorimetry is carried out using a general differential scanning calorimeter under the following test conditions. <Differential scanning calorimetry test conditions> Measurement container: Aluminum sample pan Sample amount and size: Adjust appropriately according to the size of the sample pan mentioned above. Measurement start temperature: 0℃ End of measurement temperature: 120℃ Temperature rise rate: set in the range of 0.01 to 20° C. / min, preferably in the range of 5 to 10° C. / min. Measurement procedure: First, the sample is heated from room temperature to 120°C, and when it reaches 120°C, it is cooled to -5°C. Next, after the sample temperature reaches -5°C, it is heated from 0°C to 120°C at a specified heating rate, and a DSC curve is obtained.

[0027] The melting peak temperature of the crosslinked polymer 110 is not particularly limited, but is preferably 33.0 to 58.0°C. In particular, when the complex is operated in contact with the surface of a living body as a wearable device or the like, the peak melting temperature of the crosslinked polymer 110 is preferably 33.0 to 37.0°C, more preferably 34.0 to 36.5°C, taking into consideration the temperature of the surface of the living body. On the other hand, when the complex is operated while being placed or indwelled in a living body, the peak melting temperature of the crosslinked polymer 110 is preferably 37.0 to 45.0°C, taking into consideration the temperature inside the body, and more preferably, is more than 37.0°C and 44.0°C or less.

[0028] The degree of crystallinity of the crosslinked polymer 110 is not particularly limited, but the degree of crystallinity obtained by differential scanning calorimetry is preferably 10.0 to 40.0%. When the complex is driven on the surface of a living body, the degree of crystallinity of the crosslinked polymer 110 is preferably 10.0 to 15.5%. When the complex is driven inside a living body, the degree of crystallinity of the crosslinked polymer 110 is preferably more than 15.5% and not more than 40.0%, more preferably more than 15.5% and not more than 28.0%, and further preferably the lower limit is more than 15.5%.

[0029] The crosslinked polymer 110 is not particularly limited as long as it has the above-mentioned crystallinity. In the following, an exemplary embodiment of a curable compound (crosslinkable monomer) for obtaining a cured product suitable for the crosslinked polymer 110 contained in the composite 100 of this embodiment and a method for producing the same will be described.

[0030] <Curable compound 1> In one exemplary embodiment, the crosslinked polymer 110 is a cured product of a curable compound 1 represented by the following formula 1:

[0031] [ka]

[0032] In formula 1, L 1 represents a poly(oxyalkylenecarbonyl) group, and X 1 represents a group having a curable group, R 1 represents a hydrogen atom or the above-mentioned monovalent substituent not having a curable group, q1 represents an integer of 2 or more, p1 represents an integer of 0 or more, and when q1 is 2 and p1 is 0, M 1 represents a single bond or a divalent group, and when q1 is 2 and p1 is 1 or more, and when q1 is 3 or more, M 1 represents a p1+q1 valent group, and multiple R 1 , and L 1 may be the same or different.

[0033] L in Equation 1 1The poly(oxyalkylenecarbonyl) group is a divalent group consisting of a polymer chain having oxyalkylenecarbonyl groups as repeating units, and specifically, is a group represented by the following formula II.

[0034] [ka]

[0035] In formula II, L 21 represents an alkylene group, L 21 The number of carbon atoms in the alkylene group is not particularly limited, but is preferably 1 to 20, and more preferably 2 to 10. Among these, L is preferred because it can provide a composite having superior effects according to the present invention. 21 As the alkylene group, an alkylene group having 2 to 10 carbon atoms is more preferable.

[0036] In addition, in the formula II, n represents a number of 2 or more, and is not particularly limited, but is preferably 2 to 200, more preferably 2 to 100, further preferably 5 to 50, and particularly preferably 10 to 30.

[0037] As described later, the curable compound 1 can also be prepared by ring-opening polymerization of a cyclic ester. In this case, the number n can be adjusted by the charging ratio of a ring-opening polymerization initiator (e.g., a polyhydric alcohol) and a monomer (e.g., a lactone compound). More specifically, the lactone compound is charged so that the desired number n reacts with one hydroxyl group of the polyhydric alcohol.

[0038] The above number n is the 1 It can be determined by H-NMR (Nuclear Magnetic Resonance) measurement.

[0039] Returning to equation 1, X 1 is a group having a curable group. In this specification, the group having a curable group means the curable group itself or an atomic group having a curable group as a partial structure in its structure. X 1The group having a curable group is not particularly limited, but is preferably a group represented by the following formula (III).

[0040] [ka]

[0041] In formula III, Z represents a curable group; L 3 represents a single bond or a divalent group. Also, "*" represents the bond position. L 3 The divalent group is not particularly limited, and may be -C(O)-, -C(O)O-, -OC(O)-, -O-, -S-, -NR 20 -(R 20 represents a hydrogen atom or a monovalent organic group), an alkylene group (preferably having 1 to 10 carbon atoms), a cycloalkylene group (preferably having 3 to 10 carbon atoms), an alkenylene group (preferably having 2 to 10 carbon atoms), and combinations thereof. Among these, L is particularly preferred in that it can provide a composite having the excellent effects of the present invention. 3 is a single bond, -O-, -C(O)-, an alkylene group, or -NR 20 - and combinations thereof are preferred.

[0042] In formula III, the curable group of Z refers to a group involved in a curing reaction. The curable group is not particularly limited, but is preferably a radical polymerizable group, and more preferably a group having an ethylenically unsaturated bond, in that a composite having a better effect of the present invention can be obtained. The group having an ethylenically unsaturated bond is not particularly limited, but examples thereof include a (meth)acryloyl group, a styryl group, and an allyl group, and among them, a (meth)acryloyl group is preferred. In this specification, "(meth)acryloyl" means either one or both of acryloyl and methacryloyl.

[0043] Returning to Equation 1, M 1 As the p+q valent group, M 1 When L is a divalent group, its form is not particularly limited, but3 The divalent groups already explained above are preferred.

[0044] M 1 When is a trivalent or higher valent group, there is no particular limitation, and examples thereof include groups represented by the following formulas (4a) to (4d).

[0045] [ka]

[0046] In formula 4a, L3 represents a trivalent group. T3 represents a single bond or a divalent group, and three T3 may be the same or different. Examples of L3 include a nitrogen atom, a trivalent hydrocarbon group (preferably having 1 to 10 carbon atoms. The hydrocarbon group may be an aromatic hydrocarbon group or an aliphatic hydrocarbon group), or a trivalent heterocyclic group (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L3 include a glycerol residue, a trimethylolpropane residue, a phloroglucinol residue, and a cyclohexanetriol residue.

[0047] In formula 4b, L4 represents a tetravalent group. T4 represents a single bond or a divalent group, and the four T4 may be the same or different. Suitable forms of L4 include a tetravalent hydrocarbon group (preferably having 1 to 10 carbon atoms. The hydrocarbon group may be an aromatic hydrocarbon group or an aliphatic hydrocarbon group) and a tetravalent heterocyclic group (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L4 include a pentaerythritol residue and a ditrimethylolpropane residue.

[0048] In formula 4c, L5 represents a pentavalent group. T5 represents a single bond or a divalent group, and five T5 may be the same or different. Suitable forms of L5 include pentavalent hydrocarbon groups (preferably having 2 to 10 carbon atoms. The hydrocarbon group may be an aromatic or aliphatic hydrocarbon group) or pentavalent heterocyclic groups (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L5 include an arabinitol residue, a phloroglucidol residue, and a cyclohexanepentanol residue.

[0049] In formula 4d, L6 represents a hexavalent group. T6 represents a single bond or a divalent group, and six T6 may be the same or different. Suitable forms of L6 include a hexavalent hydrocarbon group (preferably having 2 to 10 carbon atoms. The hydrocarbon group may be an aromatic or aliphatic hydrocarbon group) or a hexavalent heterocyclic group (preferably a 6- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L6 include a mannitol residue, a sorbitol residue, a dipentaerythritol residue, a hexahydroxybenzene residue, and a hexahydroxycyclohexane residue.

[0050] In the formulae 4a to 4d, the divalent groups represented by T3 to T6 are the same as those already described above. 1 It may be the same as or the same as the divalent group. Also, M 1 When is a group with a valence of 7 or more, a group formed by combining the groups represented by formulae 4a to 4d can be used.

[0051] Returning to formula 1, p1 represents an integer of 0 or more, preferably 2 or less, more preferably 1 or less, and further preferably 0. In addition, q1 represents an integer of 2 or more, preferably 4 or less, more preferably 3 or less, and further preferably 2.

[0052] In formula 1, R 1 represents a hydrogen atom or a monovalent substituent not having the above-mentioned curable group. The monovalent substituent not having a curable group is not particularly limited, and examples thereof include a group represented by *-L"-R'. In the above formula, L″ represents a single bond or a divalent group, R′ represents a hydrogen atom or a hydrocarbon group (which may be linear, branched, or cyclic), and * represents the bonding position.

[0053] The curable compound 1 is preferably a compound represented by the following formula 1B, in that a composite having a more excellent effect of the present invention can be obtained.

[0054] [ka]

[0055] In formula 1B, M 1B is a 1-valent group, and its form, including the preferred form, is the same as that of M in formula 1 already described. 1 The above is the same as the group represented by the following formula: L 1B represents a poly(oxyalkylenecarbonyl) group, and X 1B represents a group having a curable group, and the form thereof, including the preferred form, is the same as that of L in Formula 1 already described above. 1 , and X 1 is the same as:

[0056] In terms of obtaining a composite having even more excellent effects of the present invention, the curable compound 1 is preferably a compound represented by the following formula 1D.

[0057] [ka]

[0058] In formula 1D, AL 2 represents an alkylene group having 1 to 20 carbon atoms. The number of carbon atoms in the alkylene group is not particularly limited, but is preferably 3 or more and 10 or less. Drepresents a hydrocarbon having 1 to 5 carbon atoms, and is preferably at least one group selected from the group consisting of -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, and -CH2C(CH3)2CH2-, and more preferably -CH2CH2CH2CH2-. X 1D represents a group having a curable group, and its form, including the preferred form, is the same as X in formula 1 described above. 1 The above is the same as the group represented by the following formula:

[0059] In formula 1D, w represents an integer of 2 or more, preferably an integer of 100 or less, more preferably an integer of 50 or less, and more preferably an integer of 20 or less.

[0060] The number average molecular weight of the curable compound 1 is not particularly limited, but in general, a value of 2,000 to 8,000 is preferred. The molecular weight distribution (Mw / Mn) of the curable compound 1 is not particularly limited, but is generally preferably 1.1 to 1.6. The number average molecular weight and weight average molecular weight of the curable compound 1 refer to values ​​determined by GPC (Gel Permeation Chromatography) measurement according to the method described in the Examples below.

[0061] <Curable compound 2> In another exemplary embodiment, the crosslinked polymer 110 is a cured product of a curable compound 2 represented by Formula 2 below:

[0062] [ka]

[0063] L 2 represents a polymer chain, the polymer chain including a repeating unit composed of an oxyalkylenecarbonyl group, a repeating unit derived from D-lactic acid, and a repeating unit derived from L-lactic acid; 2 is X in Equation 1 1 represents a group having the same curable group as that represented by R 2represents a hydrogen atom or the above-mentioned monovalent substituent not having a curable group, q2 represents an integer of 2 or more, p2 represents an integer of 0 or more, and when q2 is 2 and p2 is 0, M 2 represents a single bond or a divalent group, and when q2 is 2 and p2 is 1 or more, and when q2 is 3 or more, M 2 represents a p2+q2-valent group, and multiple R 2 , and L 2 may be the same or different.

[0064] L in Equation 2 2 The polymer chain of is a polymer chain that contains all of the repeating units consisting of oxyalkylenecarbonyl groups, the repeating units derived from D-lactic acid, and the repeating units derived from L-lactic acid. 2 The polymer chain may have repeating units other than those mentioned above, in which case it is preferably a poly(oxyalkylene) group (chain).

[0065] Lactic acid exists as two optical isomers, L-lactic acid and D-lactic acid, which are represented by the following formula. Polylactic acid polymers can be obtained by polyesterification of these.

[0066] Typically, lactic acid can be polymerized by being converted to a cyclic lactide as shown in the following formula and then subjected to ring-opening polymerization. In this specification, the repeating unit of the polymer derived from this D-lactic acid is referred to as a "repeating unit derived from D-lactic acid" and the repeating unit of the polymer derived from L-lactic acid is referred to as a "repeating unit derived from L-lactic acid."

[0067] [ka]

[0068] Therefore, L 2The polymer chain has a repeating unit P1 (a repeating unit consisting of an oxyalkylene carbonyl group) represented by the following formula, P2D (a repeating unit derived from D-lactic acid), and P2L (a repeating unit derived from L-lactic acid). In the following formula, n represents an integer of 1 to 20, preferably an integer of 2 to 10, and more preferably an integer of 3 to 8.

[0069] [ka]

[0070] L 2 The order of arrangement of the P1 unit, P2D unit, and P2L unit in the polymer chain is not particularly limited, and may be random, triblock, or multiblock. 2 From the viewpoint of making it easier to control the melting point of the polymer chain of L to a lower level, it is preferable that the polymer chain is randomly arranged (is a random copolymer). 2 In the cured product (crosslinked product), these polymer chains become polymer chains located between crosslinking points, but if the arrangement of the repeating units of this polymer chain is random, the polymer chain will not easily take on a regular folded structure or an extended chain structure, and the melting point of the cured product will be lower or the cured product will have no melting point (no crystallinity).

[0071] L 2 The contents of P1 units, P2D units, and P2L units in are not particularly limited, but when the total content of each unit is taken as 100 mol%, the content of P1 units may be 1 to 10 mol%, 10 mol% or more, 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, or 60 mol% or more. When the crosslinked polymer is composed only of a cured product of the curable compound 2, L 2 The content of P1 units in the above formula (I) is preferably more than 60 mol % and less than 100 mol %. The upper limit may be 90 mol % or less, 80 mol % or less, or 70 mol % or less. The content of the P2D unit and the P2L unit may be 1 to 5 mol%, 5 mol% or more, 10 mol% or more, or 15 mol% or more. The upper limit may be 45 mol% or less, 40 mol% or less, 35 mol% or less, 30 mol% or less, 25 mol% or less, or 20 mol% or less. When the crosslinked polymer is composed only of a cured product of the curable compound 2, L 2 The content of P2D units and P2L units in each of the above formulas is preferably 1 mol % or more and less than 20 mol %. In this case, the upper limit of each of the above contents may be 15 mol % or less, 10 mol % or less, or 5 mol % or less.

[0072] The number of repetitions of the P1 unit, P2D unit, and P2L unit in the polymer chain is not particularly limited, but from the viewpoint of making the deformation rate of the cured product larger, the number of repetitions is preferably 10 or more, more preferably 20 or more, and even more preferably 30 or more, and is preferably 200 or less, more preferably 100 or less, and even more preferably 70 or less.

[0073] In an exemplary preferred embodiment, L 2 The total number of repetitions of the P1 unit, the P2D unit, and the P2L unit is 10 to 100.

[0074] Returning to Equation 2, X 2 is a group having a curable group. 2 The curable group contained in the compound represented by the formula 1 is X 1 In addition, X 2 Specific examples of the group X 1 The preferred embodiments are also the same as those of the group represented by the formula (I). Also, R 2 The monovalent substituent of R in formula 1 is also 1 The monovalent substituents are the same as those in the above, and the preferred embodiments are also the same. Also, M 2 The divalent group and the trivalent or higher group are also represented by M 1The divalent group and the trivalent or higher valent group are the same as those mentioned above, and the preferred embodiments are also the same.

[0075] In formula 2, p2 represents an integer of 0 or more, preferably 2 or less, more preferably 1 or less, and even more preferably 0. Furthermore, q2 represents an integer of 2 or more, preferably 3 or more, more preferably 8 or less, and more preferably 6 or less.

[0076] The curable compound 2 is preferably a compound represented by the following formula 1C, in that a composite having a more excellent effect of the present invention can be obtained.

[0077] [ka]

[0078] In formula 1C, M 1C is a divalent group, L 1C represents a polymer chain, the polymer chain containing all of a repeating unit consisting of an oxyalkylenecarbonyl group, a repeating unit derived from D-lactic acid, and a repeating unit derived from L-lactic acid (and may further contain a poly(oxyalkylene) group); X 1C is X in formula 1B 1B represents a group having the same curable group as that represented by r2, r2 represents an integer of 2 or more, and 1C may be the same or different.

[0079] Here, L 1C Polymer chain, M1 C A divalent or trivalent or higher group, X 1C The curable group is L in formula 2. 2 Polymer chain, M 2 a divalent or trivalent or higher group, X 2 The curable groups are the same as those in the above, and the preferred forms are also the same. r2 is preferably an integer of 2 or more, and is preferably not more than 10, more preferably not more than 8, and even more preferably not more than 6. When r2 is within the above numerical range, a composite having better effects of the present invention can be obtained.

[0080] From the viewpoint of obtaining a composite having a more excellent effect of the present invention, the curable compound 2 is preferably a compound represented by the following formula 1E.

[0081] [ka]

[0082] In formula 1E, L 1Ea represents a polymer chain, and includes all of a repeating unit consisting of an oxyalkylenecarbonyl group, a repeating unit derived from D-lactic acid, and a repeating unit derived from L-lactic acid, 1Eb represents a single bond or a polymer chain consisting of a poly(oxyalkylene) group (chain), and X 1E is X in Equation 1D 1D represents a group having the same curable group as

[0083] Here, L 1E The polymer chain of X 1E The group having a curable group is represented by L in formula 2. 2 The polymer chain of X 2 The same groups as those having a curable group as mentioned above can be mentioned, and the preferred forms are also the same.

[0084] The number average molecular weight of the curable compound 2 is not particularly limited, but is generally preferably 8000 to 40000. The molecular weight distribution (Mw / Mn) of the curable compound is not particularly limited, but is generally preferably 1.10 to 1.80. The number average molecular weight and weight average molecular weight of the curable compound 2 refer to values ​​determined by GPC (Gel Permeation Chromatography) measurement according to the method described in the Examples below.

[0085] <Method of producing curable compound> Here, a method for producing the curable compound 1 and the curable compound 2 (hereinafter, these are also collectively referred to simply as "curable compounds") will be described. The method for producing the curable compound is not particularly limited, but a method in which a group having a curable group is introduced into a precursor compound obtained by ring-opening polymerization of a cyclic compound is preferred in that the curable compound can be obtained more simply.

[0086] As the cyclic compound, a known cyclic compound can be used, and is not particularly limited, but is preferably one that can be ring-opened by hydrolysis. For example, cyclic esters (lactone compounds) such as β-propiolactone, β-butyrolactone, β-valerolactone, γ-butyrolactone, γ-valerolactone, γ-caprylolactone, δ-valerolactone, β-methyl-δ-valerolactone, δ-stearolactone, ε-caprolactone, γ-octanoic lactone, 2-methyl-ε-caprolactone, 4-methyl-ε-caprolactone, ε-caprylolactone, ε-palmitolactone, α-hydroxy-γ-butyrolactone, and α-methyl-γ-butyrolactone; cyclic diesters such as glycolide and lactide; and the like can be mentioned.

[0087] Among these, the cyclic compound is preferably a lactone compound or lactide in terms of good reactivity in ring-opening polymerization, and the lactone compound is more preferably at least one selected from the group consisting of β-propiolactone, β-butyrolactone, β-valerolactone, γ-butyrolactone, γ-valerolactone, γ-caprylolactone, δ-valerolactone, β-methyl-δ-valerolactone, δ-stearolactone, ε-caprolactone, 2-methyl-ε-caprolactone, 4-methyl-ε-caprolactone, ε-caprylolactone, and ε-palmitolactone.

[0088] In particular, lactide can be used for the synthesis of the curable compound 2, and examples of this lactide include L-lactide (LL-lactide) formed by dehydration condensation of two molecules of L-lactic acid, D-lactide (DD-lactide) formed by dehydration condensation of two molecules of D-lactic acid, meso-lactide formed by dehydration condensation of one molecule of L-lactic acid and one molecule of D-lactic acid, and DL-lactide (racemic lactide) which is an equal mixture of D-lactide and L-lactide, etc. DL-lactide is preferred in that the melting point of the obtained cured product tends to be lower.

[0089] The method for obtaining a precursor compound by ring-opening polymerization of a cyclic compound is not particularly limited, but examples thereof include a method for ring-opening polymerization using an alcohol as an initiator in the presence of a metal catalyst.

[0090] Metal catalyst The metal catalyst is not particularly limited, but examples thereof include fatty acid salts, carbonates, sulfates, phosphates, oxides, hydroxides, halides, and alcoholates of alkali metals, alkaline earth metals, rare earths, transition metals, aluminum, germanium, tin, and antimony. More specifically, examples of the compounds include stannous chloride, stannous bromide, stannous iodide, stannous sulfate, stannic oxide, stannous myristate, stannous octoate (Tin (II)-ethylhexanoate), stannous stearate, tetraphenyltin, tin methoxide, tin ethoxide, stannous butoxide, aluminum oxide, aluminum acetylacetonate, aluminum isopropoxide, aluminum-imine complex, titanium tetrachloride, ethyl titanate, butyl titanate, glycol titanate, titanium tetrabutoxide, zinc chloride, zinc oxide, diethylzinc, antimony trioxide, antimony tribromide, antimony acetate, calcium oxide, germanium oxide, manganese oxide, manganese carbonate, manganese acetate, magnesium oxide, and yttrium alkoxide.

[0091] The amount of the metal catalyst used was 0.01 × 10 per mole of the cyclic compound, calculated as the metal element in the metal catalyst. -4 ~100×10 -4Molar amounts are preferred.

[0092] Initiator The initiator is not particularly limited, but may be a monohydric or dihydric or higher alcohol.

[0093] The monohydric alcohol is not particularly limited, but R IN Alcohols represented by -OH are included, and R IN represents an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent. The aliphatic hydrocarbon group is not particularly limited, but examples thereof include alkyl groups having 1 to 20 carbon atoms. Examples of monohydric alcohols include methanol, ethanol, n-propyl alcohol, n-butyl alcohol, sec-butyl alcohol, pentyl alcohol, n-hexyl alcohol, cyclohexyl alcohol, octyl alcohol, nonyl alcohol, 2-ethylhexyl alcohol, n-decyl alcohol, n-dodecyl alcohol, hexadecyl alcohol, lauryl alcohol, ethyl lactate, and hexyl lactate.

[0094] Examples of dihydric or higher alcohols (polyhydric alcohols) include ethylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, trimethylolethane, ditrimethylolethane, trimethylolpropane, ditrimethylolpropane, pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, diglycerol, and pentaerythritol ethoxylate.

[0095] Among these, dihydric alcohols or tetrahydric alcohols are preferred in that they provide a composite having a more excellent effect of the present invention, and the dihydric alcohol is preferably at least one selected from the group consisting of ethylene glycol, 1,3-propanediol, 1,4-butanediol, and neopentyl glycol. As the tetrahydric alcohol, pentaerythritol, pentaerythritol ethoxylate, and the like are preferable. The amount of the initiator used is not particularly limited, but is preferably about 0.0001 to 0.1 mol per 1 mol of the cyclic compound.

[0096] ·Ring-opening polymerization The ring-opening polymerization is preferably carried out under an inert gas atmosphere in order to prevent the volatilization of the cyclic compound. The polymerization temperature is not particularly limited, but is preferably 100 to 250°C. The polymerization time is not particularly limited, but is preferably about 0.1 to 48 hours.

[0097] -Introduction of curable groups The method of introducing a curable group into a precursor compound obtained by ring-opening polymerization of a cyclic compound is not particularly limited, and examples thereof include a method (a) of reacting a compound having both a substituent reactive to a hydroxy group possessed by the precursor compound and a curable group, and a method (b) of substituting a hydroxy group possessed by the precursor compound with another functional group, and reacting a compound having both a functional group reactive to the substituent and a curable group, etc. Among them, the method (a) is preferred in that a curable compound (macromonomer) can be obtained more easily.

[0098] In the above method (i), the compound to be reacted with the hydroxy group of the precursor compound is not particularly limited, but examples thereof include unsaturated acid halogen compounds such as (meth)acrylic acid chloride and (meth)acrylic acid bromide when the curable group is a (meth)acryloyl group. The amount of the compound to be reacted with the hydroxy group of the precursor compound is not particularly limited, but is preferably about 0.1 to 20 molar equivalents relative to the hydroxy group.

[0099] <Curing compound composite> In another exemplary embodiment, the crosslinked polymer 110 is a cured product of a composite of the curable compounds composed of the above-mentioned Curable Compound 1 and the above-mentioned Curable Compound 2.

[0100] The contents of the curable compound 1 and the curable compound 2 in the composite of the curable compounds are not particularly limited as long as they have the above-mentioned crystallinity. For example, the contents of the curable compound 1 and the curable compound 2 can be adjusted in consideration of the use of the composite so that the melting peak temperature of the crosslinked polymer falls within a desired range.

[0101] Specifically, the content of the curable compound 1, in relation to the curable compound 2, when the total is taken as 100 mol %, is preferably 20 mol % or more, more preferably 30 mol % or more, even more preferably 35 mol % or more, and particularly preferably 40 mol % or more. The upper limit is preferably 99 mol % or less, more preferably 95 mol % or less, further preferably 90 mol % or less, and particularly preferably 85 mol % or less.

[0102] In particular, when the complex is to be actuated on the surface of a living body, the content of the curable compound 1 is preferably 45 to 65 mol %. When the complex is operated in vivo, the content of the curable compound 1 is preferably 65 to 99 mol %, and more preferably 65 to 85 mol %.

[0103] The content of the curable compound 2, in relation to the curable compound 1, when the total is taken as 100 mol%, is preferably 1 mol% or more, more preferably 5 mol% or more, even more preferably 10 mol% or more, particularly preferably 15 mol% or more, preferably 80 mol% or less, more preferably 70 mol% or less, even more preferably 65 mol% or less, particularly preferably 60 mol% or less.

[0104] In particular, when the complex is to be actuated on the surface of a living body, the content of the curable compound 2 is preferably 35 to 50 mol %. When the complex is operated in vivo, the content of the curable compound 2 is preferably 1 to 35 mol %, and more preferably 10 to 35 mol %.

[0105] In an exemplary preferred embodiment, in the above-mentioned composite of curable compounds, the molar ratio of the content of curable compound 2 to the contents of curable compound 1 and curable compound 2 ([curable compound 2] / [curable compound 1+curable compound 2]) is 0.01 to 0.65.

[0106] In another exemplary preferred embodiment, from the viewpoint of enabling the cured product of the composite of the curable compounds to have both a lower melting point and a higher deformation rate, it is preferred that the test specimen prepared by the following method does not have crystallinity.

[0107] Preparation method of the test specimen: 500 mg of the curable compound 2, 15 mg of benzoyl peroxide, and 695 μL of xylene are mixed to obtain a composition, which is then heated to 80° C. to polymerize it. The resulting polymer is washed with acetone, shrunk in methanol, and then dried under reduced pressure to obtain a test specimen.

[0108] <Cured product> As a shape-memory material suitable for the crosslinked polymer 110 contained in the composite 100 of this embodiment, the above-mentioned cured product of the curable compound 1, the cured product of the curable compound 2, and the cured product of the composite of the curable compound composed of the curable compound 1 and the above-mentioned curable compound 2 can be obtained by a method that is not particularly limited, but can be obtained by applying energy (typically, heating) to a composition containing the curable compound 1 and the curable compound 2, and other components as necessary, to cure the composition. Details will be described in the section on "Manufacturing method of the composite" below.

[0109] [Metal Nanowires] The material of the metal nanowires (hereinafter also simply referred to as "metal nanowires") 120 included in the composite 100 of this embodiment is a metal. The metal as the material of the metal nanowires 120 does not include ceramics such as metal oxides and nitrides. Specific examples include iron, cobalt, nickel, copper, zinc, ruthenium, rhodium, palladium, silver, cadmium, osmium, iridium, platinum, and gold. Among these, from the viewpoint of electrical conductivity, copper, silver, platinum, and gold are preferable, and silver is more preferable.

[0110] The shape of the metal nanowire 120 is not particularly limited as long as the ratio of the length in the short axis direction to the length in the long axis direction (hereinafter also referred to as the "aspect ratio") is 10 or more, but from the viewpoint of synthesis of the metal nanowire and production of the composite, if the aspect ratio is too large, handling may become difficult. Therefore, the aspect ratio is preferably 10,000 or less, and more preferably 1,000 or less.

[0111] The metal nanowire 120 may be linear, branched, or have a shape in which particles are linked together like beads, or may have a mixture of these shapes. Here, a linear metal nanowire means that the shape is rod-like, and a branched metal nanowire means that the shape is branched. Note that when the metal nanowire has low rigidity and is partially or entirely curved or bent, it is included in the linear metal nanowire.

[0112] The length of the metal nanowire 120 in the short axis direction is not particularly limited, but is preferably 1 nm or more and 1 μm or less. If the length in the short axis direction is too short, it is likely to be difficult to synthesize the metal nanowire, so it is more preferably 10 nm or more and 500 nm or less. The length of the metal nanowire in the long axis direction is not particularly limited, but from the viewpoint of electrical conductivity, it is preferably 1 μm or more and 1 mm or less. In addition, if the length in the long axis direction is too long, it may be difficult to handle, so it is more preferably 10 μm or more and 100 μm or less. The shape and size of the metal nanowires 120 can be confirmed by a scanning electron microscope or a transmission electron microscope.

[0113] The metal nanowire 120 can be synthesized by a known method. For example, there is a method of reducing silver nitrate in a solution, and a method of continuously forming the metal nanowire by applying a voltage or current from the tip of a probe to the surface of a precursor and drawing out the metal nanowire at the tip of the probe. Specific examples of the method of reducing silver nitrate in a solution include a method of reducing nanofibers made of metal-complexed peptide lipids (JP Patent Publication 2002-266007), a method called polyol reduction, in which reduction is performed while heating in ethylene glycol (Y. Sun, et al., Chem Mater., 2002, 14(11), 4736-4745.), and a method of reduction in sodium citrate (KK Caswell, et al., Nano Lett., 2003, 3(5), 667-669.). Among them, the method of reduction while heating in ethylene glycol is preferable because it allows the synthesis of metal nanowires with high crystallinity with relative ease.

[0114] The content of the metal nanowires 120 in the composite 100 of this embodiment is not particularly limited, and may be an amount sufficient to drive the composite 100 by localized heating caused by application of a current.

[0115] Specifically, the content of the metal nanowires 120 calculated by thermogravimetry (TG) is preferably 5% or more, more preferably 10% or more, even more preferably 15% or more, and even more preferably 20% or more. As a result, the metal nanowires 120 can be incorporated into the crosslinked polymer 110 in the composite 100 in a state where they are dispersed to such an extent that the composite 100 can be driven by localized heating due to application of electric current. The thermogravimetry is performed by the method described in the examples below.

[0116] On the other hand, since the composite 100 of the present embodiment has one of its features that it can be driven by local heating due to application of electric current, the content of the metal nanowires 120 does not need to be higher than necessary. From this viewpoint, the content of the metal nanowires 120 calculated by thermogravimetry (TG) is preferably 60% or less, more preferably 50% or less, even more preferably 40% or less, and even more preferably 35% or less. By setting the content of the metal nanowires 120 to a lower value, it is possible to avoid adverse effects such as Joule heat generated by application of electric current being transmitted to the surrounding environment unintentionally. On the other hand, depending on the application of the composite, there may be cases where it is not necessary to take the above-mentioned propagation and diffusion of Joule heat to the surrounding environment into consideration. Therefore, as long as the composite has conductivity sufficient to enable measurement of electrical resistance, the content of metal nanowires 120 may be 5% or more and 60% or less, 5% or more and 50% or less, 5% or more and 40% or less, 5% or more and 35% or less, 10% or more and 35% or less, 15% or more and 35% or less, or 20% or more and 35% or less.

[0117] [Conductivity of the composite] As described above, the composite 100 of this embodiment has a structure in which the metal nanowires 120 are incorporated into the crosslinked polymer 110, and therefore has conductivity sufficient to enable measurement of electrical resistance in both the permanent and temporary shapes.

[0118] The electrical conductivity test of a composite is performed by preparing a test piece of any size and measuring the electrical resistance (Ω) under at least three conditions: in its permanent shape (before deformation), when stretched 100% using a tensile tester, and when contracted 100% by applying energy (typically by heating) (when the composite has recovered to approximately the same size as before deformation). Specific test methods when the test piece is in a sheet form are as described in the Examples below. When the test piece is in a shape other than a sheet form, a person skilled in the art can appropriately modify the design.

[0119] [Structural stability of the complex] As described above, the composite 100 of this embodiment has a structure in which the metal nanowires 120 are incorporated into the crosslinked polymer 110, and therefore has excellent structural stability.

[0120] Specifically, in a stability test using a good solvent for the crosslinked polymer 110 and / or the metal nanowires 120, the composite 100 does not substantially cause detachment of the metal nanowires 120.

[0121] Here, "substantially no detachment of metal nanowires" means that in visual observation of the test solvent before and after the stability test, suspension of the test solvent due to the metal nanowires detached from the composite is not substantially observed, and / or in weight measurement of the test piece before and after the stability test, no weight loss due to the metal nanowires detached from the composite is observed. In practice, since some test solvent may remain in the test piece after the stability test, the weight of the test piece made from the composite 100 of this embodiment after the test may be substantially the same as the weight before the test, or may be slightly increased compared to the weight before the test. On the other hand, in the test piece made from a material that does not have a structure such as the composite 100 of this embodiment, the weight after the test is clearly reduced compared to the weight before the test.

[0122] The solvent used in the stability test, i.e., the good solvent for the crosslinked polymer 110 and / or the metal nanowires 120, is not particularly limited and may be appropriately selected depending on the structure, material, etc. of the crosslinked polymer and / or the metal nanowires. Specific examples include alcohols such as methanol, ethanol, and 1-propanol. Specific test methods when the test piece is in a sheet form are as described in the Examples below. When the test piece is in a shape other than a sheet form, a person skilled in the art can appropriately modify the design.

[0123] [Method of manufacturing the composite] There are no particular limitations on the manufacturing method for the composite 100 of this embodiment, but the following manufacturing method is preferred in that it can more easily obtain a composite that can be applied to a shape memory member that can be driven by localized heating through the application of an electric current.

[0124] The method for producing a composite according to one embodiment of the present invention (hereinafter also referred to as the "production method of this embodiment") is as follows: A step of producing a molded body including metal nanowires (hereinafter also referred to as a "molded body production step"); A step of applying a composition containing a curable compound to the molded body (hereinafter also referred to as a "composition application step"); A step of applying energy to the molded article to which the composition is applied, thereby curing the curable compound (hereinafter also referred to as a "curing step"); Includes. Each of the above steps will be described below.

[0125] (Molded body production process) The molded body preparation step is a step of preparing a molded body containing metal nanowires. Specifically, a metal nanowire dispersion solution is prepared by dispersing metal nanowires in a solvent, and the metal nanowire dispersion solution is applied to a support, and the solvent is dried at a predetermined temperature to obtain a molded body containing metal nanowires.

[0126] The solvent for dispersing the metal nanowires is not particularly limited, and examples thereof include alcohols such as methanol, ethanol, and 1-propanol, and organic solvents that are liquid at room temperature and have high volatility, such as DMF (N,N-dimethylformamide).

[0127] (Composition application process) The composition applying step is a step of applying a composition containing a curable compound to the molded body obtained in the molded body producing step.

[0128] The curable compound contained in the above composition is not particularly limited, but is preferably selected from the group consisting of the above-mentioned curable compound 1, curable compound 2, and a composite of curable compounds composed of curable compound 1 and the above-mentioned curable compound 2.

[0129] The composition may contain other components as necessary, so long as it contains the above-mentioned curable compound. Examples of the other components include a curing agent and a solvent.

[0130] <Hardening agent> A curing agent is a compound that acts on a curable compound to cause a curing reaction. The curing agent is not particularly limited, and known compounds can be used, typically radical polymerization initiators are preferred. As the curing agent, a heat curing agent in which a curing reaction proceeds by applying heat energy and / or a light curing agent in which a curing reaction proceeds by applying light (applying light energy) can be used.

[0131] Examples of the heat curing agent include azo compounds such as azobisisobutyronitrile, and peroxides such as benzoyl peroxide. Examples of the photocuring agent include aromatic ketone compounds such as benzophenone, Michler's ketone, xanthone, and thioxanthone; quinone compounds such as 2-ethylanthraquinone; acetophenone compounds such as acetophenone, trichloroacetophenone, 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, benzoin ether, 2,2-diethoxyacetophenone, and 2,2-dimethoxy-2-phenylacetophenone; and methylbenzoyl formate. diketone compounds, such as 1-phenyl-1,2-propanedione-2-(O-benzoyl)oxime; acyloxime ester compounds, such as 1-phenyl-1,2-propanedione-2-(O-benzoyl)oxime; acylphosphine oxide compounds, such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide; sulfur compounds, such as tetramethylthiuram and dithiocarbamate; organic oxides, such as benzoyl peroxide; azo compounds, such as azobisisobutyronitrile; organic sulfonium salt compounds; iodonium salt compounds; phosphonium compounds; and the like.

[0132] The content of the curing agent in the composition is preferably 0.001 to 10% by mass based on the total mass of the curable compounds in the composition. The composition may contain one type of curing agent alone or two or more types. When the composition contains two or more types of curing agents, the total content is preferably within the above numerical range.

[0133] <Solvent> The composition may contain a solvent. The solvent contained in the composition is not particularly limited, but it is sufficient to select a solvent that can dissolve and / or disperse the curable compound and the curing agent and that does not easily evaporate during the curing reaction. For example, when benzoyl peroxide (BPO) is used as a curing agent, the temperature of the curing reaction is about 80° C., so a solvent with a boiling point equal to or higher than the curing reaction temperature is preferred. By using such a solvent, evaporation of the solvent during the curing reaction can be further suppressed, so that a cured product with fewer air bubbles is likely to be obtained. Examples of such solvents include xylene, butyl acetate, DMF, and dimethyl sulfoxide.

[0134] On the other hand, when a photocuring agent is used as the curing agent, the temperature of the curing reaction is generally lower than when a thermal curing agent is used, so that even if a solvent with a lower boiling point is used, a cured product with fewer air bubbles can be obtained. Examples of the solvent that can be used include dichloromethane, chloroform, and acetone.

[0135] The content of the solvent in the composition is not particularly limited, but when the composition contains a solvent, it is preferably 10 to 90% by mass when the total mass of the composition is 100% by mass. The composition may contain one type of solvent alone, or may contain two or more types. When the composition contains two or more types of solvents, the total content is preferably within the above numerical range.

[0136] (hardening process) The curing step is a step of applying energy to the molded article to which the composition is applied, thereby curing the curable compound.

[0137] In the curing step, the type of energy to be applied to the molded body may be appropriately selected depending on the type of curing agent that can be contained in the above-mentioned composition, and heating and / or light irradiation are preferred.

[0138] The method for applying energy is not particularly limited, but examples include a method in which a molded body formed on a support is heated and / or the molded body is irradiated with light to cure the curable compound. The heating temperature, heating time, and light irradiation intensity, irradiation time, etc. may be appropriately selected depending on the shape of the molded body, the type of curing agent, etc. More specifically, the heating temperature may be, for example, 40 to 200° C. Furthermore, the heating time may be, for example, 1 minute to 24 hours.

[0139] The energy may be applied to the molded body under pressure. This allows the metal nanowires to be more efficiently incorporated into the crosslinked structure of the cured product during the curing process of the curable compound. As a result, the resulting composite is likely to have a structure in which the metal nanowires are effectively embedded in the crosslinked structure of the crosslinked polymer. The pressure to be applied may be appropriately adjusted depending on the shape and thickness of the molded body.

[0140] Furthermore, the manufacturing method of this embodiment may include a step of drying the obtained product (a composite containing metal nanowires and a cured product of the curable compound) after the above-mentioned curing step (hereinafter also referred to as a "drying step").

[0141] The drying step is a step of drying the product to remove at least a part of the solvent contained in the product. The drying method is not particularly limited, and examples thereof include a method of leaving the product at rest at 20 to 50° C. for 1 minute to 24 hours, and a method of maintaining the product under reduced pressure. The drying conditions may be appropriately selected depending on the shape and thickness of the product.

[0142] The size and shape of the present cured product are not particularly limited. They may be appropriately determined depending on the application. The present cured product has a shape memory function, a lower driving temperature, and an excellent deformation rate, and therefore can be applied to medical instruments such as ligatures and sutures. The present cured product can also be used as a film by taking advantage of its shape memory function. For example, if the film is used as the base material of an adhesive tape having a base material and an adhesive layer disposed on the base material, it can be preferably used as a medical tape.

[0143] [Shape memory material] Although there is no particular limitation on the method of using the composite 100 of this embodiment, as described above, the composite 100 of this embodiment has a shape memory ability by including the crosslinked polymer 110. The composite 100 of this embodiment can be fixed in a temporary shape by heating it to a softening point (a temperature near the melting temperature of the crystal) under stress and then cooling it. Thereafter, when the composite 100 in the temporary shape is reheated to its softening point, it returns to a permanent shape. In addition, the composite 100 of this embodiment can be driven by local heating by applying an electric current by including the metal nanowire 120 (more specifically, the metal nanowire 120 is incorporated in the crosslinked polymer 110). Thus, the composite 100 of this embodiment is suitable for producing a member including the composite 100 and using it as an electrically driven shape memory member.

[0144] Specifically, it can be used as a component of an apparatus, tool, etc., such as a wearable device, that is applied to the surface of a living body, or as a component of an apparatus, tool, etc., that is applied inside a living body. Alternatively, the composite of the present embodiment can be used alone or in combination with other components depending on the desired application. EXAMPLES

[0145] The present invention will now be described in further detail with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0146] 1. Synthesis and analysis of curable compounds 1-1. [Synthesis of curable compound 1 (2b20PCL macromonomer)] Curable compound 1 (2b20PCL macromonomer) was synthesized based on the following scheme. First, the divalent ring-opening polymerization initiators 1,4-butanediol (2.21 mL, 0.025 mol) and ε-caprolactone (CL) (105.6 mL, 1 mol) and the catalyst tin(II)-2 ethylhexanoate (0.2 mL) were added to a round-bottom flask and reacted at 120°C for 24 hours under a nitrogen atmosphere.

[0147] The reaction product was then reprecipitated in a mixed solvent of hexane and diethyl ether in a 1:1 volume ratio and dried under reduced pressure to obtain 2-branched 20-mer PCL (hereinafter also referred to as "2b20PCL").

[0148] Next, 10 times the amount of acryloyl chloride (17.7 mL, 0.22 mol) and 11 times the amount of triethylamine (33.2 mL, 0.24 mol) were added to the terminal group of the recovered 2b20PCL (50 g, 0.011 mol) and reacted for 72 hours. After that, the mixture was purified by reprecipitation in methanol and dried under reduced pressure to recover the curable compound 1 (2b20PCL macromonomer), which is a macromonomer of 2b20PCL.

[0149] [ka]

[0150] The molecular weight of "2b20PCL" and the number of repeating oxyalkylenecarbonyl groups were determined by GPC and 1 The test conditions were as follows: The number average molecular weight of 2b20PCL determined from the GPC results was 3700 and Mw / Mn was 1.23.

[0151] GPC measurement conditions Measuring device: (Tosoh) HLC-8220GPC Detector: Refractive index (RI) detector Column used: "Shodex (trademark)" GPC LF-804 (80 mm I.D. x 300 mm x 2 columns) Column temperature: 40℃ Eluent: DMF, flow rate 0.5mL / min Sample: Dissolve in DMF at 0.2% by mass and filter through a 0.45 μm membrane filter. Molecular weight standard polymer: polystyrene (molecular weight = 1970, 3930, 7920, 12140, and 21030), 0.1 mass%

[0152] ·NMR measurement conditions Measurement equipment: 400MHz NMR (JEOL) Solvent: Deuterated chloroform (CDCl3) Sample concentration: ~30mg / mL (3mass / vol%) Reference material: Tetramethylsilane (TMS) Measurement Method: 1 H measurement resonance frequency 400MHz Observed spectral width: 0ppm~10ppm Number of times accumulated: 128 times Measurement temperature: room temperature (20~25℃)

[0153] 1-2. [Synthesis of curable compound 2 (4b50P(CL-co-DLLA))] Based on the following scheme, the synthesis of curable compound 2 (a copolymer of CL and d,l-lactide (DLLA)) was carried out. First, the tetravalent ring-opening polymerization initiator pentaerythritol (343 mg, 0.0025 mol), ε-caprolactone (32 mL, 0.3 mol), DLLA (14.5 g, 0.2 mol), and catalyst Tin(II) 2-ethylhexanoate (0.2 mL) were added to a round-bottom flask and reacted at 140°C for 24 hours under a nitrogen atmosphere to obtain 4-branched 50-mer P(CL-co-DLLA). Hereinafter, this will be referred to as "4b50P(CL-co-DLLA)".

[0154] Then, 10 times the amount of acryloyl chloride and 11 times the amount of triethylamine were added to the terminal group, and the mixture was allowed to react for 72 hours. After that, the mixture was purified by reprecipitation in methanol and dried under reduced pressure to recover the curable compound 2 (4b50P(CL-co-DLLA) macromonomer), which is a macromonomer of 4b50P(CL-co-DLLA). In the following scheme, m:n is a molar ratio of 6:4.

[0155] The number average molecular weight of 4b50P (CL-co-DLLA) measured by GPC was 9900, and the Mw / Mn was 1.44.

[0156] [ka]

[0157] 1-3. [Preparation of cured product] A composition was prepared using the curable compound 1 and the curable compound 2, and the composition was heated and cured to obtain a cured product. Table 1 shows the composition formulation. A composition was obtained by completely dissolving 500 mg of the curable compounds 1 and 2 in total, and 15 mg of BPO (3 mass / volume % based on the total of the curable compounds) as a radical polymerization initiator (curing agent) in 695 μL of xylene.

[0158] Next, this composition was dropped onto a glass substrate, sandwiched between another glass substrate via a 0.2 mm thick polytetrafluoroethylene spacer, and left to stand overnight (3 hours or more) in an oven at 80° C. to cure. The resulting cured product was thoroughly washed with acetone, shrunk in methanol, and then dried under reduced pressure (overnight).

[0159] [DSC measurement] DSC measurements were performed to measure the melting peak temperature and crystallinity of the crystals of the obtained cured product. The DSC measurements were performed using a differential scanning calorimeter (heat flux type) "X-DSC 7000" manufactured by SII Corporation. The test conditions were as follows.

[0160] Measurement container: Aluminum sample pan (φ6.8mm) Sample amount and size: The sample amount was approximately 10 mg, and was cut to fit into the sample pan.

[0161] Starting temperature: 0℃ Heating rate: 5℃ / min End temperature: 120℃

[0162] First, each sample (cured material) was heated from room temperature to 120°C, and when it reached 120°C, it was cooled to -5°C. Next, after the temperature of the sample reached -5°C, it was heated from 0°C to 120°C at a rate of 5°C / min, and the DSC curve was obtained.

[0163] The melting peak temperature (Tm) of the crystals read from the obtained DSC curve and the degree of crystallinity are shown in Table 1. The degree of crystallinity was calculated by calculating the enthalpy (ΔH) from the endothermic peak area, and then the formula (degree of crystallinity) = (ΔH / 142) x 100. Each value was calculated to two decimal places and rounded off.

[0164] [Measurement of elastic modulus] The elastic modulus was calculated from the linear portion of the stress-strain curve obtained by the tensile test. The test piece was a sheet with a length of 17.5±2.5 mm, a width of 5.00±0.90 mm, and a thickness of 0.14±0.03 mm. The test was performed at room temperature with a tensile speed of 5 mm / min. Each value was calculated to two decimal places and rounded off.

[0165] The lower the elastic modulus, the greater the deformation when the same force is applied. The higher the breaking strain, the less likely the cured material is to break even when subjected to a large deformation. From the above, a cured material with both a smaller elastic modulus and a larger breaking strain has a larger deformation rate as a shape memory material. In addition, the "ratio" in Table 1 indicates the molar ratio of the content of curable compound 2 to the contents of curable compound 1 and curable compound 2 in the composition ([curable compound 2] / [curable compound 1 + curable compound 2]).

[0166] [Table 1]

[0167] From the results in Table 1, the cured products of Examples 1 to 6 obtained by curing the compositions containing Curable Compound 1 and Curable Compound 2 all had crystallinity and had a deformation ratio that could be used as a shape-memory material. Among them, the cured products of Examples 1 to 5 had a small elastic modulus and a large breaking strain, and had a large deformation ratio as a shape-memory material.

[0168] More specifically, the cured products of the compositions of Examples 3 and 4 had higher crystal melting peak temperatures (Tm) than the cured products of the compositions of Examples 1 and 2, and had lower crystal melting peak temperatures (Tm) than the cured product of the composition of Example 5, both of which were in the range of 37.0 to 45.0°C, making them more suitable for applications in vivo (such as ligatures).

[0169] Furthermore, the cured products of the compositions of Examples 1 and 2 had lower crystal melting peak temperatures (Tm) than the cured product of the composition of Example 3, and the temperatures were also in the range of 33.0 to 37.0°C, making them more suitable for applications that require actuation on the surface of a living body (wearable devices, sutures, etc.).

[0170] Furthermore, the cured products of the compositions of Examples 1 and 2, which had a degree of crystallinity in the range of 10.0 to 15.5%, had a lower peak melting temperature (Tm) of the crystals compared to the cured product of the composition of Example 3, and the temperature was also in the range of 33.0 to 37.0°C, making them more suitable for applications that are driven on the surface of a living body (wearable devices, sutures, etc.).

[0171] Furthermore, the cured products of the compositions of Examples 3 and 4, which had a degree of crystallinity in the range of more than 15.5% and not more than 40.0%, had a higher peak melting temperature (Tm) of the crystals than the cured products of the compositions of Examples 1 and 2, and a lower peak melting temperature (Tm) of the crystals than the cured product of the composition of Example 5, both of which were in the range of 37.0 to 45.0°C, and were therefore more suitable for applications in which the product is operated within a living body (such as a ligature device).

[0172] 2. Synthesis and Analysis of Metal Nanowires 2-1. [Synthesis of silver nanowires 1] Silver nanowires were synthesized according to the following procedure. Poly vinylpyrrolidone (PVP) (494 mg, 34 mM), ethylene glycol (160 mL, 2.9 mM), and CuCl2 (0.43 mg, 4 mM) were added to a round-bottom flask, and AgNO3 (480 mg, 94 mM) was added dropwise over 30 min. The mixture was then stirred for 1 hour to synthesize silver nanowires.

[0173] The obtained silver nanowire solution was centrifuged (3500 rpm, 20 min), the supernatant was removed, and the silver nanowires were redispersed in ethanol. This procedure was repeated three times to purify the silver nanowires, and the product silver nanowires were collected.

[0174] 2-2. [Synthesis of silver nanowires 2] Silver nanowires were synthesized according to the following procedure. Poly vinylpyrrolidone (PVP) (900 mg), ethylene glycol (150 mL), FeCl3 (0.43 mg), and AgNO3 (600 mg) were added to a round-bottom flask and stirred until dissolved. After dissolution, the mixture was heated to 110°C in an oil bath and reacted for 24 hours without stirring to synthesize silver nanowires.

[0175] Acetone was added to the obtained silver nanowire solution in a 1:1 ratio, centrifuged (3500 rpm, 15 min), the supernatant was removed, and the solution was redispersed in ethanol. This process was repeated three times to purify the silver nanowires, and the product silver nanowires were collected.

[0176] 2-3. [Analysis of silver nanowires] The silver nanowires synthesized in 2-1 and 2-2 above were subjected to thermogravimetry (TG) under the following measurement conditions:

[0177] ·TG measurement conditions Measurement equipment: TG / DTA6200 (Seiko Instruments) Heating rate: 10℃ / min Measurement temperature range: 25~600℃ Atmosphere gas: Nitrogen Sample weight (mass): 2.3 mg

[0178] As a result, a weight change (mass loss) of 12% was observed in all samples upon heating, confirming that the silver nanowires synthesized in this example were coated with 12% PVP by mass.

[0179] In addition, SEM observation of the silver nanowires was performed using a scanning electron microscope (JCM-500 Neoscope, manufactured by JEOL Ltd.). Figures 2(a) and (b) are SEM images of the silver nanowires synthesized in 2-1 and 2-2 above, respectively. The scale bar in Figure 2(a) is 5 μm, and the scale bar in Figure 2(b) is 20 μm. 2(a) and (b), the silver nanowires synthesized in this example had a high aspect ratio. Specifically, the silver nanowires synthesized in 2-2 above had an average minor axis length of about 150 nm, an average major axis length of about 30 μm, and an average aspect ratio calculated to be about 200.

[0180] 3. Preparation and analysis of the complex (part 1) 3-1. [Preparation of Complex 1] The complex was prepared according to the following procedure. 20 mg of the silver nanowires synthesized in 2-1 above was dispersed in 4 mL of ethanol to prepare a silver nanowire suspension. This silver nanowire suspension was cast onto a glass substrate, and the ethanol was dried at room temperature to produce a silver nanowire film.

[0181] Next, using the curable compound 1 (2b20PCL macromonomer) synthesized in 1-1 above as the curable compound constituting the crosslinked polymer, 500 mg of 2b20PCL macromonomer and 15 mg of BPO (3 mass / volume % relative to the macromonomer) as a radical polymerization initiator (curing agent) were completely dissolved in 695 μL of xylene to prepare a composition. This composition was dropped onto a silver nanowire film prepared on a glass substrate, sandwiched between another glass substrate via a 0.2 mm thick polytetrafluoroethylene spacer (4 cm × 4 cm), and left to stand overnight (more than 3 hours) in an oven at 80 ° C. to cure the 2b20PCL macromonomer, and a sheet-like composite with a length of 3 cm, width of 3 cm, and thickness of 0.012 cm was prepared.

[0182] 3-2. [Preparation of Complex 2] The complex was prepared according to the following procedure. A curable compound (4-branched 50-mer PCL (hereinafter, also referred to as "4b50PCL")) macromonomer was synthesized in the same manner as in 1-1 above, except that pentaerythritol, a tetravalent ring-opening polymerization initiator, was used as the ring-opening polymerization initiator. 500 mg of 4b50PCL macromonomer and 15 mg of BPO (3 mass / volume % relative to the macromonomer) as a radical polymerization initiator (curing agent) were completely dissolved in 695 μL of xylene to prepare a composition. This composition was dropped onto a glass substrate, sandwiched between another glass substrate via a 0.2 mm thick polytetrafluoroethylene spacer (4 cm x 4 cm), and left to stand overnight (3 hours or more) in an oven at 80 ° C. to cure the 4b50PCL macromonomer, producing a sheet-like cured product with a length of 3 cm, a width of 3 cm, and a thickness of 0.016 cm.

[0183] A composition was prepared using 4b50PCL in the same manner as in 1-3 above, and the composition was heated and cured to obtain a cured product, which had a melting peak temperature (Tm) of 55.3°C and a crystallinity of 31.3%.

[0184] Here, the prepared cured product was heated to above its melting point, stretched 300% in the width direction from its original shape using a tensile tester, and then cooled in this state, whereby the stretched shape was fixed.

[0185] Next, 11.14 mg of the silver nanowires synthesized in 2-1 above was dispersed in 1 mL of ethanol to prepare a silver nanowire suspension solution. This silver nanowire suspension solution was evenly cast in 0.1 mL portions onto one surface of the cured product with the stretched shape fixed, and then dried. This cycle was repeated 10 times to produce a composite.

[0186] 3-3. [Preparation of Complex 3] The complex was prepared according to the following procedure. 12.8 mg of the silver nanowires synthesized in 2-1 above was dispersed in 350 μL of DMF to prepare a silver nanowire suspension solution. Into this silver nanowire suspension, the curable compound 1 (2b20PCL macromonomer) (250 mg) synthesized in 1-1 above and 7.5 mg of BPO (3 mass / volume % with respect to the macromonomer) as a radical polymerization initiator (curing agent) were completely dissolved. The solution containing the obtained silver nanowires and 2b20PCL macromonomer was dropped onto a glass substrate, sandwiched between another glass substrate via a 0.2 mm thick polytetrafluoroethylene spacer (4 cm x 4 cm), and left to stand overnight (more than 3 hours) in an oven at 80°C to harden the 2b20PCL macromonomer, producing a sheet-like composite measuring 3 cm in length, 3 cm in width, and 0.014 cm in thickness.

[0187] In addition, composites were prepared by the same procedure as above, except that the amount of silver nanowires dispersed in DMF was 62 mg and 84.7 mg.

[0188] 3-4. [Preparation of Complex 4] The complex was prepared according to the following procedure. 15 mg of the silver nanowires synthesized in 2-2 above was dispersed in 1 mL of ethanol to prepare a silver nanowire suspension. This silver nanowire suspension was cast onto a glass substrate, and the ethanol was dried at room temperature to produce a silver nanowire film. Here, a rectangular mold (inner dimensions: length 3 cm, width 3 cm, depth 0.37 cm) made of PDMS (polydimethylsiloxane) was placed on the glass substrate in advance, and the silver nanowire suspension was cast inside the mold.

[0189] Next, using the curable compound 1 (2b20PCL macromonomer) synthesized in 1-1 above as the curable compound constituting the crosslinked polymer, 500 mg of 2b20PCL macromonomer and 15 mg of BPO (3 mass / volume % relative to the macromonomer) as a radical polymerization initiator (curing agent) were completely dissolved in 695 μL of xylene to prepare a composition. This composition was dropped onto a silver nanowire film prepared on a glass substrate, sandwiched between another glass substrate via a 0.2 mm thick polytetrafluoroethylene spacer (4 cm × 4 cm), and left to stand overnight (more than 3 hours) in an oven at 80 ° C. to cure the 2b20PCL macromonomer, and a sheet-like composite with a length of 3 cm, width of 3 cm, and thickness of 0.012 cm was prepared.

[0190] In addition, composites were prepared by the same procedure as above, except that the amount of silver nanowires dispersed in ethanol was 10 mg and 5 mg.

[0191] 3-5. [Preparation of Complex 5] The complex was prepared according to the following procedure. Using the curable compound 1 (2b20PCL macromonomer) synthesized in 1-1 above, 500 mg of 2b20PCL macromonomer and 15 mg of BPO (3 mass / volume % relative to the macromonomer) as a radical polymerization initiator (curing agent) were completely dissolved in 695 μL of xylene to prepare a composition. This composition was dropped onto a glass substrate, sandwiched between another glass substrate via a 0.2 mm thick polytetrafluoroethylene spacer (4 cm × 4 cm), and left to stand overnight (3 hours or more) in an oven at 80 ° C. to cure the 2b20PCL macromonomer, producing a sheet-like cured product with a length of 3 cm, a width of 3 cm, and a thickness of 0.015 cm.

[0192] Here, a rectangular test piece measuring 2 cm in length and 1 cm in width was cut from the prepared cured product.

[0193] Next, 10 mg of the silver nanowires synthesized in 2-2 above was dispersed in 1 mL of ethanol to prepare a silver nanowire suspension solution. This silver nanowire suspension solution was evenly cast on one surface of the test piece cut from the cured product in 0.05 mL (50 μL) portions and dried, and this cycle was repeated 10 times to prepare a composite.

[0194] 3-6. [Preparation of Complex 6] The complex was prepared according to the following procedure. Using the curable compound 1 (2b20PCL macromonomer) synthesized in 1-1 above, 500 mg of 2b20PCL macromonomer and 15 mg of BPO (3 mass / volume % relative to the macromonomer) as a radical polymerization initiator (curing agent) were completely dissolved in 695 μL of xylene to prepare a composition. This composition was dropped onto a glass substrate, sandwiched between another glass substrate via a 0.2 mm thick polytetrafluoroethylene spacer (4 cm × 4 cm), and left to stand overnight (3 hours or more) in an oven at 80 ° C. to cure the 2b20PCL macromonomer, producing a sheet-like cured product with a length of 3 cm, a width of 3 cm, and a thickness of 0.015 cm.

[0195] Here, strip-shaped test pieces measuring 2 cm in length and 1 cm in width were cut from the cured material thus produced, heated above the melting point, and stretched 100% in the vertical direction from its original shape using a tensile testing machine, and then cooled in this state to fix the stretched shape.

[0196] Next, 10 mg of the silver nanowires synthesized in 2-2 above was dispersed in 1 mL of ethanol to prepare a silver nanowire suspension solution. This silver nanowire suspension solution was uniformly cast on one surface of the test piece with the stretched shape fixed, at 0.05 mL (50 μL) each, and then dried. This cycle was repeated 10 times to produce a composite.

[0197] [Procedure for preparing the complex] Here, the procedures for producing the complex in the above 3-1 to 3-6 can be roughly classified into the following three types. Preparation procedure A: A composition containing a curable compound is applied to a molded body of metal nanowires prepared on a support, and then energy is applied to cure the curable compound. Preparation procedure B: A composition containing a curable compound is applied onto a support, and energy is applied to cure the curable compound to produce a cured product, to which a suspension solution of metal nanowires is applied. · Preparation step C: A mixed solution containing metal nanowires and a curable compound is applied onto a support, and then energy is applied to cure the curable compound.

[0198] In Tables 2 to 5 described later, for convenience, the preparation procedure of each example of the composite is shown using the above preparation procedure symbols A to C. It should be noted that, similarly, hereinafter, the preparation procedure of each example of the composite may be referred to using the above preparation procedure symbols A to C.

[0199] 3-7. [Analysis of the complex] [TG measurement 1] The composites prepared in 3-1 and 3-3 above were subjected to thermogravimetry (TG) to calculate the content of silver nanowires in each composite. The results are shown in Table 2. The measurement conditions are as follows.

[0200] ·TG measurement conditions Measurement equipment: TG / DTA6200 (Seiko Instruments) Heating rate: 10℃ / min Measurement temperature range: 25~600℃ Atmosphere gas: Nitrogen Sample weight (mass): 5.3 mg (n = 3)

[0201] [Drive test 1 by applying current] In addition, strip-shaped test pieces measuring 3 cm in length and 0.5 cm in width were cut from the composites prepared in 3-1 to 3-3 above, heated to above the melting point, and stretched 100% in the vertical direction using a tensile tester, and then cooled in that state to fix the stretched shape. In that state, alligator clips were clamped to both ends of each test piece in the vertical direction, and a voltage was applied to check whether or not they returned to their original shape. The results are shown in Table 2.

[0202] [Table 2]

[0203] The results shown in Table 2 suggest that it is difficult to obtain a composite that can be driven by applying a current in the case of fabrication procedure C. More specifically, in the case of fabrication procedure C, a composite with a higher silver nanowire content was obtained than in the case of fabrication procedure A, but recovery to the original shape was not observed in the drive test. On the other hand, the composites obtained by fabrication procedures A and B were able to recover to their original shape during the drive test. In particular, the composite obtained by fabrication procedure A (composite 3-1) was able to repeat deformation and recovery at least three times by applying a voltage of 0.88 V (applied current of 0.12 A).

[0204] This suggests that in the preparation of the composite of the present invention, it is preferable that the formation of the crosslinked structure of the crosslinked polymer and the formation of the network structure of the metal nanowires are not simultaneous, but have a time lag. In particular, as in the preparation procedure A, a composition containing a curable compound constituting a crosslinked polymer is applied to a molded body of metal nanowires with a network structure formed therein, and then energy is applied to cure the curable compound, so that the metal nanowires are easily incorporated into the crosslinked polymer in a state where they are dispersed to an extent that the composite can be driven by local heating due to application of electric current. In other words, in an embodiment in which the composite of the present invention has a sheet-like shape, as long as the metal nanowires are incorporated into at least one surface of the crosslinked polymer, the composite can be driven by local heating due to application of electric current, and it is not essential that the metal nanowires are incorporated throughout the entire crosslinked polymer.

[0205] In addition, in the above 3-1, where preparation procedure A was applied, when the curable compound was cured, the silver nanowire film to which the composition was applied was sandwiched between glass substrates, and it is believed that the application of a certain pressure allowed the incorporation of the metal nanowires into the crosslinked structure of the crosslinked polymer to proceed more efficiently.

[0206] Figures 3(a) and (b) are SEM images of the surface (surface where silver nanowires are embedded) and cross section of the composite prepared in 3-1 above, respectively. The scale bar in Figure 3(a) is 50 μm, and the scale bar in Figure 3(b) is 200 μm. As shown in Figures 3(a) and (b), in the composite of 3-1, it was confirmed that the metal nanowires were incorporated into the crosslinked polymer in a dispersed state to such an extent that the composite could be driven by localized heating due to the application of electric current.

[0207] Here, a rectangular test piece measuring 3 cm in length and 0.5 cm in width was cut from the composite prepared in 3-1 above, and alligator clips were attached to both ends of the test piece in the vertical direction using a DC power source (REGULATED DC POWER SUPPLY LX010-3.5 B TAKASAGO) to investigate the relationship between power and temperature. As specific test conditions, the current value was increased by 0.5 A at a time, and the temperature at that time was plotted while maintaining the power for 15 seconds. The test was performed at a temperature range of 25 to 130°C.

[0208] The results are shown in Figure 4. FIG. 4 is a graph showing the relationship between power (W) and temperature (° C.) for the composite prepared in 3-1 above. As shown in Figure 4, in the composite of 3-1, the temperature increased with increasing power (increasing current value), and it was confirmed that the structure of the crosslinked polymer was damaged when the temperature exceeded approximately 130°C. From this result, it was found that the temperature of the composite can be controlled by adjusting the power (applied current) supplied to the composite.

[0209] On the other hand, the composite obtained by Preparation Procedure B (composite 3-2) exhibited heat generation behavior and recovery to its original shape upon application of a higher voltage (8 V) than the composite obtained by Preparation Procedure A (composite 3-1). From this, it can be said that even by applying (a suspension of) metal nanowires to a crosslinked polymer in which a crosslinked structure has been formed, as in Preparation Procedure B, it may be possible to disperse metal nanowires in the composite to an extent that the composite can be driven by localized heating due to application of electric current. However, as will be described later, there may be issues regarding structural stability in the composite obtained by Preparation Procedure B.

[0210] [Stability test 1: Stability in permanent form] Next, the structural stability of the composites prepared in the above 3-3 to 3-5 was tested in a permanent shape. For the composites 3-3 and 3-4, the silver nanowire contents calculated by thermogravimetry (TG) were 26.7% (see Table 2) and 17.3±2.5% (see Table 4 described later), respectively, and rectangular test pieces of the same size as the composite 3-5, 2 cm long and 1 cm wide, were cut out and used for this test. The test procedure is as follows.

[0211] Each of the three types of test pieces was immersed in a 10 mL sample tube containing 5 mL of ethanol, which is a good solvent for silver nanowires. At this time, no particular changes were observed in any of the test pieces when visually observed. Next, each sample tube was vibrated to cause stirring. Visual observation revealed no particular changes in the test pieces of composites 3-3 and 3-4, but detachment of silver nanowires was observed in the test piece of composite 3-5. Furthermore, each sample tube was subjected to ultrasonic treatment for 1 minute using an ultrasonic cleaner (US-105, manufactured by SND Corporation). As a result, no particular changes were observed in the test pieces of the composites 3-3 and 3-4 by visual observation, but the test piece of the composite 3-5 showed suspension of the solvent due to the detached silver nanowires. The above results are shown in Table 3.

[0212] Here, the change in weight of the test piece before and after the above-mentioned stability test 1 will be described. In the test pieces of the composites 3-3 and 3-4, where no detachment of silver nanowires was observed by visual observation, an increase in weight of about 0.2 to about 0.5 mg was observed before and after the test, which is thought to be due to partial retention of ethanol, the test solvent. On the other hand, in the test piece of the composite of 3-5, where the detachment of the silver nanowires was clearly observed by visual observation, a weight loss of about 3 mg was observed before and after the test, and the weight of the test piece after the test was almost the same as the weight after cutting the test piece from the cured product in the above-mentioned preparation procedure of 3-5. That is, in the test piece of the composite of 3-5, it is considered that almost all of the silver nanowires constituting the composite were detached from the crosslinked polymer by the above-mentioned stability test 1. In fact, the appearance of the test piece after the test did not have the metallic luster due to the silver nanowires, and had the same properties as the permanent shape of the cured product of the 2b20PCL macromonomer.

[0213] [Stability test 2: Stability in temporary form] Next, the structural stability of the composites prepared in the above 3-3, 3-4, and 3-6 in a temporary shape was tested. For the composites 3-3 and 3-4, samples having the same silver nanowire content as used in Stability Test 1 above were used, and rectangular test pieces 2 cm long and 1 cm wide, the same size as the composite 3-6, were cut out, heated above the melting point, and stretched 100% in the vertical direction from their original shape using a tensile testing machine before cooling. The stretched shape was then fixed and used in this test.

[0214] The test procedure was the same as that of Stability Test 1 described above, so a detailed explanation is omitted. The test results were also similar to those of the above-mentioned Stability Test 1. Specifically, when each of the above three types of test pieces was immersed in a 10 mL sample tube containing 5 mL of ethanol, which is a good solvent for silver nanowires, no particular changes were observed in any of the test pieces by visual observation. Next, each sample tube was vibrated to cause stirring. Visual observation revealed no particular changes in the test pieces of composites 3-3 and 3-4, but detachment of silver nanowires was observed in the test piece of composite 3-6. Furthermore, each sample tube was subjected to ultrasonic treatment for 1 minute using an ultrasonic cleaner (US-105, manufactured by SND Corporation). As a result, no particular changes were observed in the test pieces of the composites 3-3 and 3-4 by visual observation, but the test piece of the composite 3-6 showed suspension of the solvent due to the detached silver nanowires. The above results are shown in Table 3.

[0215] The weight change of the test pieces before and after the above-mentioned stability test 2 also showed the same tendency as in the above-mentioned stability test 1. Specifically, the test pieces of the composites 3-3 and 3-4, which did not show any detachment of silver nanowires by visual observation, showed an increase in weight of about 0.1 to about 0.6 mg before and after the test. This is thought to be due to partial residue of ethanol, the test solvent. On the other hand, in the test piece of the composite of 3-6, where the detachment of the silver nanowires was clearly observed by visual observation, a weight loss of about 1.3 mg was observed before and after the test, and the weight of the test piece after the test was almost the same as the weight after cutting the test piece from the cured product in the preparation procedure of 3-6 above. That is, in the test piece of the composite of 3-6, it is considered that almost all of the silver nanowires constituting the composite were detached from the crosslinked polymer by the above stability test 2. In fact, the appearance of the test piece after the test did not have the metallic luster of the silver nanowires, and had the same properties as the temporary shape of the cured product of the 2b20PCL macromonomer.

[0216] [Table 3]

[0217] [TG measurement 2] Next, the composites prepared in 3-4 above were subjected to thermogravimetry (TG) to calculate the content of silver nanowires in each composite. The results are shown in Table 4. The measurement conditions are as follows.

[0218] ·TG measurement conditions Measurement equipment: TG / DTA6200 (Seiko Instruments) Heating rate: 10℃ / min Measurement temperature range: 25~550℃ Atmosphere gas: Nitrogen Sample weight (mass): 3 mg (n = 2)

[0219] [Drive test 2 by applying current] In addition, strip-shaped test pieces measuring 3 cm in length and 0.5 cm in width were cut from the composites prepared in 3-4 above, heated above the melting point, and stretched 100% in the vertical direction using a tensile tester, and then cooled in that state to fix the stretched shape. In that state, alligator clips were clamped to both ends of each test piece in the vertical direction, and a voltage was applied to check whether or not they would return to their original shape. The results are shown in Table 4.

[0220] [Table 4]

[0221] The results shown in Table 4 suggest that even in the case of fabrication procedure A, a certain amount of silver nanowires is necessary to obtain a composite that can be driven by the application of electric current. In other words, it was suggested that the composite obtained by fabrication procedure A will be a composite that can be driven by the application of electric current if the silver nanowire content in the composite is a certain value or more. The amount of metal nanowires required for these fabrication procedures and the metal nanowire content in the composite are thought to depend on the shape and size of the target composite, but the inner dimensions of the PDMS mold used in 3-4 above, more specifically, an area of ​​3 cm length x 3 cm width (9 cm 2 ), it can be said that by using at least more than 5 mg of metal nanowires (silver nanowires), a network structure can be formed in which the silver nanowires are dispersed to such an extent that the composite can be driven by local heating due to application of a current. In addition, in a composite in which metal nanowires (silver nanowires) having a network structure thus formed are incorporated into the crosslinked structure of a crosslinked polymer, the content of silver nanowires can be about 5% or more, preferably 10% or more.

[0222] 5(a) to (f) are diagrams showing SEM images of the surfaces of the three types of composites produced in 3-4 above in the permanent shape (before deformation) and the temporary shape (after deformation). Figures 5(a) to (c) show SEM images of the surface (the surface on which the silver nanowires are embedded) of composites in their permanent shape (before deformation) prepared using 5 mg, 10 mg, and 15 mg of silver nanowires, respectively. Figures 5(d) to (f) show SEM images of the surfaces (surfaces on which the silver nanowires are embedded) of composites in temporary shapes (after deformation) prepared using 5 mg, 10 mg, and 15 mg of silver nanowires, respectively. The scale bars in Figures 5(a), (c), (d) and (e) are 10 µm, the scale bar in Figure 5(b) is 20 µm, and the scale bar in Figure 5(f) is 5 µm.

[0223] As shown in Figures 5(a) to (c), in the permanent shape (before deformation), no noticeable difference was observed in the dispersion state of the silver nanowires among the three types of composites with different silver nanowire contents (different amounts of silver nanowires used in preparing the composites). On the other hand, as shown in Figures 5(d) to (f), in the temporary shape (after deformation), the dispersion state of the silver nanowires (the degree of overlap between silver nanowires) appeared to be less in the SEM image of Figure 5(d) compared to Figures 5(e) and (f).

[0224] These results suggest that in order for the composite of the present invention to be driven by the application of electric current, it is necessary for the network structure of the metal nanowires to be maintained to a certain extent not only in the permanent shape but also in the desired deformed state (temporary shape), and that this may enable the composite to be driven by localized heating caused by the application of electric current.

[0225] [Conductivity test] Next, a rectangular test piece measuring 2 cm in length and 0.5 cm in width was cut from the composite prepared in 3-4 above, and alligator clips were attached to both ends of the test piece in the vertical direction, and the electrical resistance was measured using a source meter (2400 SourceMeter, manufactured by KEITHLEY). In addition, each test piece was heated to above its melting point, stretched 100% in the longitudinal direction using a tensile tester, and then cooled in this state to fix the stretched shape, and the electrical resistance was measured in the same manner. Furthermore, the test piece with the stretched shape fixed was heated to restore the shape, and the electrical resistance was measured in the same manner. Note that, since the intention here is to measure the electrical resistance during shape recovery, "heating" does not mean heating by applying an electric current. The results are shown in Table 5.

[0226] For comparison, the same test pieces were cut from the composites prepared in 3-3, 3-5, and 3-6 above, and the electrical resistance was measured in the same manner. Note that the composite used in 3-3 had a silver nanowire content calculated to be 26.7% by thermogravimetry (TG), which was converted to a weight of 18.2 mg. The results are shown in Table 5.

[0227] [Table 5]

[0228] In addition, the silver nanowire content values ​​of the composites 3-5 and 3-6 in Table 5 are estimated values ​​calculated based on the results of stability tests 1 and 2 described above, and the PVP content (coverage rate) confirmed by thermogravimetry (TG) of the silver nanowires described in 2-3 above.

[0229] As shown in Table 5, among the composites 3-4, the composites that did not show shape recovery by applying electric current (see Table 4) had an electrical resistance of 1.3 ± 0.18 (× 10 4) (Ω), the electrical resistance of the composite in the permanent shape after recovery from the specified deformed shape (temporary shape) was at least 1.0 × 10 4 It was suggested that it is preferable to satisfy Ω or less. In addition, in the temporary shape, the composite is stretched, and the network structure of the metal nanowires is also stretched, so the electrical resistance of the composite is larger than that in the permanent shape; however, it remains at 1.0×10 5 It was suggested that if the resistance is 0.1 Ω or less, it can be driven by applying a current. In addition, it was found that even if the content of metal nanowires in the composite is about the same, there may be a difference in the value of electrical resistance between the permanent shape before the initial deformation and the permanent shape after recovery from the temporary shape. This indicates that in the composite of the present invention, the properties of the network structure of the metal nanowires incorporated in the crosslinked structure of the crosslinked polymer (dispersion state of the metal nanowires) are related to driving by application of electric current, and it is considered that if the content of the metal nanowires is within the range of approximately 5% to 25%, more preferably 10% to 25%, the composite can be made in a dispersed state to the extent that it can be driven by local heating by application of electric current. Of course, as described above, the content of the metal nanowires may exceed 25% depending on the application of the composite, and the results in Table 5 do not deny this.

[0230] In contrast, for composite 3-3, the resistance of the test specimen was too high to measure the electrical resistance value by the above test, and this is shown in Table 5 as "ND." In the composites of 3-5 and 3-6, the electrical resistance value could be measured after the composite was produced. In the composite of 3-6, the silver nanowire suspension was applied to the cured product of the curable compound 1 constituting the crosslinked polymer in a stretched state during the production of the composite, so there is no test result corresponding to "before deformation" in Table 5, and the result of "during deformation" corresponds to the above content. From this, it can be said that in the composite obtained by production procedure B, the metal nanowires can be in a state where they are dispersed to at least an extent that allows the electrical resistance to be measured. However, in the case of composite 3-5, when the shape of the test piece was changed (in "deformed" in Table 5), it was observed that the silver nanowire layer peeled off (partially detached) from the crosslinked polymer layer, and the electrical resistance value could not be measured. In Table 5, this is shown as "ND." Therefore, for composite 3-5, the electrical resistance value during shape recovery by heating was not measured, and the test was terminated. In addition, in the case of the composite 3-6, as in the case of the composite 3-5, when the shape of the test piece was changed (at "recovery" in Table 5), the silver nanowire layer was observed to peel off (partially detached) from the crosslinked polymer layer, and the electrical resistance value could not be measured. In Table 5, this is shown as "ND." These results, as well as the results of stability tests 1 and 2 described above, suggested the superiority of preparation procedure A in terms of the complex preparation procedure.

[0231] 4. Preparation and analysis of the complex (part 2) 4-1. [Preparation of the complex] A complex was prepared according to Preparation Procedure A described above. Specifically, 10 mg of the silver nanowires synthesized in 2-2 above was dispersed in 1 mL of ethanol to prepare a silver nanowire suspension (A). This silver nanowire suspension (A) was cast onto a glass substrate, and the ethanol was dried at room temperature to produce a silver nanowire film. Here, a rectangular mold made of PDMS (inner dimensions: length 3 cm, width 3 cm, depth 0.37 cm) was placed in advance on the glass substrate, and the silver nanowire suspension (A) was cast inside the mold.

[0232] Next, the composition was prepared by completely dissolving 500 mg of 2b20PCL macromonomer and 15 mg of BPO (3 mass / volume % relative to the macromonomer) as a radical polymerization initiator (curing agent) in 695 μL of xylene using the curable compound 1 (2b20PCL macromonomer) synthesized in 1-1 above as a curable compound constituting a crosslinked polymer. This composition was dropped onto a silver nanowire film prepared on a glass substrate, sandwiched between another glass substrate via a 0.5 mm thick polytetrafluoroethylene spacer (4 cm × 4 cm), and left overnight (3 hours or more) in an oven at 80 ° C. to cure the 2b20PCL macromonomer, producing a sheet-like composite with a length of 3 cm, width of 3 cm, and thickness of 0.031 cm.

[0233] Here, in this preparation example, 20 mg of the silver nanowires synthesized in 2-2 above were dispersed in 1 mL of ethanol to prepare a silver nanowire suspension solution (B), and the type and amount of the solution (number of times of casting) to be cast onto the glass substrate were set in four different ways to prepare four types of composites in which the silver nanowire content in the silver nanowire film, i.e., the silver nanowire content in the composite, was 10 mg, 20 mg, 30 mg, and 50 mg. Specifically, the silver nanowire suspension solution (A) was used to prepare the composites with the silver nanowire content of 10 mg and 20 mg, and the silver nanowire suspension solution (B) was used to prepare the composites with the silver nanowire content of 30 mg and 50 mg. Hereinafter, these composites will also be referred to as "Complex 4(10)", "Complex 4(20)", "Complex 4(30)", and "Complex 4(50)". The greater the silver nanowire content in the silver nanowire film, the thicker the silver nanowire film produced on the glass substrate; however, the size of the final sheet-like composite was always 3 cm in length, 3 cm in width, and 0.031 cm in thickness.

[0234] 4-2. [Analysis of the complex] [DSC measurement] DSC measurements were performed on Composite 4(10), Composite 4(20), Composite 4(30), and Composite 4(50). The DSC measurements were performed using a differential scanning calorimeter (heat flux type) "X-DSC 7000" manufactured by SII Corporation. The test conditions were as follows.

[0235] Measurement container: Aluminum sample pan (φ6.8mm) Sample amount and size: The sample amount was approximately 10 mg, and was cut to fit into the sample pan.

[0236] Starting temperature: 0℃ Heating rate: 5℃ / min End temperature: 120℃

[0237] First, each sample (composite) was heated from room temperature to 120°C, and when it reached 120°C, it was cooled to -5°C. Next, after the temperature of the sample reached -5°C, it was heated from 0°C to 120°C at a rate of 5°C / min, and the DSC curve was obtained.

[0238] FIG. 6 shows DSC curves of composite 4(10), composite 4(20), composite 4(30), and composite 4(50). As shown in FIG. 6, the endothermic peak and exothermic peak were confirmed in the DSC curve of each composite sample in substantially the same temperature range. In addition, although not shown in FIG. 6, the endothermic peak and exothermic peak were confirmed in substantially the same temperature range as the DSC curve of the composite in the DSC curve of the cured product (crosslinked polymer without silver nanowires) of the curable compound 1 (2b20PCL macromonomer) prepared under the same conditions as described in 4-1 above except that the silver nanowires were not included. From these results, it was found that in the preparation procedure of the composite of this preparation example (preparation procedure A above), the incorporation of the silver nanowires into the cured product (crosslinked polymer) of the curable compound does not substantially affect the melting point or crystallinity of the crosslinked polymer contained in the composite. In other words, it was found that in the composite of this preparation example, the silver nanowires are incorporated into the crosslinked polymer in a manner that can maintain the properties of the crosslinked polymer.

[0239] As explained with reference to Figures 3(a) and (b) for the composites prepared in 3-1 above, from the SEM images of the surfaces (the surfaces where the silver nanowires were incorporated) and cross sections of Composite 4(10), Composite 4(20), Composite 4(30), and Composite 4(50), it was confirmed that in all of the composites, the silver nanowires were incorporated into the crosslinked polymer in a dispersed state to such an extent that the composite could be driven by localized heating due to the application of electric current.

[0240] [TG measurement] Next, thermogravimetry (TG) was performed on Complex 4 (10), Complex 4 (20), Complex 4 (30), and Complex 4 (50). The measurement conditions are as follows.

[0241] ·TG measurement conditions Measurement equipment: TG / DTA6200 (Seiko Instruments) Heating rate: 10℃ / min Measurement temperature range: 25~550℃ Atmosphere gas: Nitrogen Sample weight (mass): 3 mg (n = 2)

[0242] FIG. 7 shows the TG curves of complex 4(10), complex 4(20), complex 4(30), and complex 4(50). As shown in Figure 7, all composite samples showed a certain weight change (mass loss) upon heating, and the higher the silver nanowire content, the higher the percentage of mass loss (%). These results show that in the composite production procedure of this production example (production procedure A above), when producing a metal nanowire compact on a support, the content of metal nanowires in the composite can be controlled by adjusting the amount of metal nanowire suspension solution applied (amount cast onto the support) having a certain concentration.

[0243] From the TG curves shown in FIG. 7, the silver nanowire contents in Composite 4(10), Composite 4(20), Composite 4(30), and Composite 4(50) were calculated to be 5.67%, 10.42%, 22.43%, and 31.35%, respectively.

[0244] [Stability test] Next, the structural stability of Composite 4(10), Composite 4(20), Composite 4(30), and Composite 4(50) in the permanent and temporary shapes was tested under the same test conditions and procedures as those used for the composites prepared in 3-3 to 3-6 above.

[0245] As a result, no significant changes were observed in the test pieces of any of the composites upon visual inspection, and the structural stability of both the permanent and temporary shapes was confirmed.

[0246] [Conductivity test] Next, rectangular test pieces measuring 3 cm in length and 0.5 cm in width were cut from Composite 4(10), Composite 4(20), Composite 4(30), and Composite 4(50). Alligator clips were attached to both vertical ends of the test pieces, and the electrical resistance was measured using a source meter (2400 SourceMeter, manufactured by KEITHLEY). In addition, each test piece was heated to above its melting point, stretched 100% in the longitudinal direction using a tensile tester, and then cooled in this state to fix the stretched shape, and the electrical resistance was measured in the same manner. Furthermore, the electrical resistance of each test piece was similarly measured when it was stretched by 200% and 300% using a tensile tester.

[0247] As a result, it was confirmed that the test pieces obtained from all of the composites had conductivity sufficient to enable measurement of electrical resistance in both the permanent and temporary shapes. In addition, it was found that the higher the silver nanowire content (content rate) of the composite, the smaller the change (increase) in electrical resistance when the sample was stretched to 100%, 200%, and 300% using a tensile testing machine. These results suggest that if the composite is intended to be used as a shape memory material with a larger deformation ratio, it is effective to set the metal nanowire content of the composite to a higher value.

[0248] [Drive test 1 by applying current] Next, rectangular test pieces measuring 3 cm in length and 0.5 cm in width were cut from Composite 4(10), Composite 4(20), Composite 4(30), and Composite 4(50), which were heated above their melting points and stretched 300% in the longitudinal direction using a tensile tester before being cooled to fix the stretched shape. In this state, alligator clips were placed on both longitudinal ends of each test piece, and a voltage of 2.0 V was applied to check whether the test piece returned to its original shape.

[0249] As a result, it was found that the test pieces obtained from both samples were able to efficiently retain the 300% stretched state (temporary shape) (fixation rate > 99%), and also had excellent recovery performance to the original shape (permanent shape) (recovery rate > 90%).

[0250] [Drive test 2 by applying current] Next, using the same test piece as in Driving Test 1 above, a cycle of stretching 300% in the vertical direction and then restoring it to its original shape by applying a voltage of 2.0 V was repeated for a total of 20 cycles, and the stress generated in the test piece during each cycle and the electrical resistance after each cycle (after restoring to the permanent shape) were measured.

[0251] Figures 8(a) to (d) are graphs showing the stress (MPa) generated in the test specimens during each cycle as a function of the test time (s) for the test specimens obtained from Composite 4 (10), Composite 4 (20), Composite 4 (30), and Composite 4 (50), respectively. As shown in Figures 8(a) to (d), it was confirmed that the stress value was almost constant when the test pieces obtained from all of the composites were repeatedly stretched by 300% in the longitudinal direction 20 times. This means that all of the composites are mechanically (structurally) stable against at least 20 repeated deformations and recoverys due to the application of electric current under the condition of a large deformation rate of 300%. Furthermore, the electrical resistance values ​​after 1 cycle and 20 cycles for each test specimen were almost equivalent, confirming that all composites were electrically stable in addition to being mechanically (structurally) stable against repeated deformation and recovery under the above conditions. In addition, the material capable of repeated deformation and recovery of 300% at a low voltage of 2.0 V is an outstanding achievement in comparison with conventional temperature-responsive shape memory materials, and has been demonstrated for the first time by the inventors.

[0252] [Drive test 3 by applying current] Next, we conducted a driving test of the composite body by non-contact power supply using a commercially available wireless power supply device. Specifically, we assembled an electromagnetic induction type wireless power supply device with a transmitting coil and a receiving coil using a wireless power supply experiment kit (manufactured by CQ Publishing, Tech Village Select Series). Using the same test pieces as in Drive Test 1 above, each test piece was heated above its melting point and stretched 300% in the vertical direction using a tensile tester, and then cooled in this stretched state to fix the stretched shape. In this state, alligator clips were clamped to both ends of each test piece in the vertical direction, the transmitting coil and receiving coil were brought close enough together, and an alternating current was passed through the transmitting coil to generate a magnetic flux in the receiving coil, causing a current to also flow in the receiving coil, and the recovery to the original shape was confirmed.

[0253] As a result, it was confirmed that test specimens obtained from both composites were able to recover to their original shape (permanent shape) from a 300% stretched state (temporary shape), demonstrating that they could be powered by wireless power supply.

[0254] [Antibacterial Test] Next, a simple antibacterial test was carried out using Complex 4(10), Complex 4(20), Complex 4(30), and Complex 4(50) according to the following procedure.

[0255] -Preparation of agar medium In a 1L beaker, 10mg of hypopeptone, 2g of yeast extract, 1g of MgSO4·7H2O, 15g of agar, and 1L of distilled water were added and stirred. The beaker was then placed in an autoclave set at 120℃ for 20 minutes to dissolve the solute and sterilize the solution. The beaker was removed, and 20mL of the resulting solution was poured into a 90mm dish, which was then cooled to prepare an agar medium.

[0256] Test 1 (permanent shape test) Staphylococcus aureus (1.0 × 10 8 CFU / mL) were plated. As specimens, circular test pieces with a diameter of 1 cm were cut from each composite, sterilized with ethylene oxide gas (EOG), and then placed so that the surface with the silver nanowires incorporated (the surface where the silver nanowire film was located when the composite was prepared) was in contact with the agar medium. After that, the specimens were incubated for 2 days in an incubator set at 30°C, and the presence and width of a growth inhibition zone (halo) was evaluated. As a control, a similar test was performed using a cured product (crosslinked polymer without silver nanowires) of curable compound 1 (2b20PCL macromonomer) prepared under the same conditions as described in 4-1 above, except that it did not contain silver nanowires.

[0257] As a result, no halos were observed in the control crosslinked polymer, whereas more halos were observed in the specimens (specimens) obtained from Composite 4(10), Composite 4(20), Composite 4(30), and Composite 4(50) as the content (content) of silver nanowires in the composite increased. More specifically, Composite 4(20) showed a clear increase in the number of halos compared to Composite 4(10), Composite 4(30) showed more halos over a wider area of ​​the specimen than Composite 4(20), and Composite 4(50) showed even more halos throughout the entire specimen. In addition, the width of each individual halo tended to be larger in Composite 4(50).

[0258] Test 2 (temporary shape test) Staphylococcus aureus (1.0 × 10 8 CFU / mL) were plated. As a specimen, the composite 4 (50) was stretched 300% in a certain direction and cooled, and a rectangular test piece 1 cm long and 0.5 cm wide was cut from the stretched shape that was fixed, and after sterilization with EOG, it was placed so that the surface with the silver nanowires incorporated (the surface where the silver nanowire film was located when the composite was made) was in contact with the agar medium. After that, it was incubated for 2 days in an incubator set at 30°C, and the presence and width of the halo were evaluated. Here, as a control, a similar test was performed using the above-mentioned crosslinked polymer.

[0259] As a result, in the control crosslinked polymer, no halos were observed even in the temporary shape, as in the above-mentioned Test 1 (test in the permanent shape), whereas in the test piece (specimen) obtained from Composite 4 (50), halos were observed throughout the test piece in the temporary shape, with the number and width being approximately the same as in the permanent shape in Test 1. From these results, it was confirmed that the composite of the present invention can effectively exhibit the inherent properties of the metal nanowires (when the metal nanowires are silver nanowires, the properties may be antibacterial) in both the permanent and temporary shapes. [Industrial Applicability]

[0260] The composite of the present invention has a shape-memory function and can be applied to a shape-memory member that can be driven by local heating caused by application of an electric current. Therefore, compared with conventional temperature-responsive shape-memory materials, it can be applied to a wider range of applications. Specifically, for example, by adjusting the melting peak temperature of the crosslinked polymer in consideration of the surface temperature and / or internal temperature of a living body, it becomes possible to apply the composite to a living body, which was difficult with conventional temperature-responsive shape-memory materials, and it is expected to be applied to minimally invasive medical devices as an electrically driven shape-memory member. [Explanation of symbols]

[0261] 100 Complex 110 Cross-linked polymer 120 Metal Nanowires

Claims

1. A crosslinked polymer having an endothermic peak when subjected to differential scanning calorimetry (DSC); A metal nanowire; A complex comprising: the crosslinked polymer is selected from the group consisting of a cured product of a curable compound 1 represented by the following formula 1, a cured product of a curable compound 2 represented by the following formula 2, and a cured product of a composite of a curable compound composed of the curable compound 1 and the curable compound 2, In a conductivity test, the material has conductivity sufficient to measure electrical resistance at least before deformation and after being deformed by 100% or more in a specified direction by applying external stress, and In a stability test using a good solvent for the crosslinked polymer and / or the metal nanowires, the metal nanowires are not substantially detached. Complex. [Case 1] (In formula 1, L 1 represents a poly(oxyalkylenecarbonyl) group, X 1 represents a group having a curable group, R 1 represents a hydrogen atom or a monovalent substituent not having the curable group, q1 represents an integer of 2 or more, p1 represents an integer of 0 or more, when q1 is 2 and p1 is 0, M 1 represents a single bond or a divalent group, when q1 is 2 and p1 is 1 or more, and when q1 is 3 or more, M 1 represents a p1+q1 valent group, and a plurality of R 1 s and L 1 s may be the same or different.) [Case 2] (In formula 2, L 2 represents a polymer chain, the polymer chain including all of a repeating unit consisting of an oxyalkylenecarbonyl group, a repeating unit derived from D-lactic acid, and a repeating unit derived from L-lactic acid; X 2 represents a group having the same curable group as X 1 in formula 1; R 2 represents a hydrogen atom or a monovalent substituent not having the curable group; q2 represents an integer of 2 or more; p2 represents an integer of 0 or more; when q2 is 2 and p2 is 0, M 2 represents a single bond or a divalent group; when q2 is 2 and p2 is 1 or more, and when q2 is 3 or more, M 2 represents a p2+q divalent group; and a plurality of R 2 s and L 2 s may be the same or different.)

2. The composite of claim 1 , wherein the metal nanowires are silver nanowires.

3. The composite according to claim 1 , wherein the content of the metal nanowires calculated by thermogravimetry (TG) is 5% or more and 60% or less.

4. A shape memory member comprising the composite material according to any one of claims 1 to 3.

5. A method for producing the composite according to any one of claims 1 to 3, comprising the steps of: A step of producing a molded body including metal nanowires; applying a composition containing a curable compound to the molded body; A step of applying energy to the molded article to which the composition is applied, thereby curing the curable compound; Including, The method, wherein the curable compound is selected from the group consisting of a curable compound 1 represented by the following formula 1, a curable compound 2 represented by the following formula 2, and a composite of the curable compound composed of the curable compound 1 and the curable compound 2. [C3] (In formula 1, L 1 represents a poly(oxyalkylenecarbonyl) group, X 1 represents a group having a curable group, R 1 represents a hydrogen atom or a monovalent substituent not having the curable group, q1 represents an integer of 2 or more, p1 represents an integer of 0 or more, when q1 is 2 and p1 is 0, M 1 represents a single bond or a divalent group, when q1 is 2 and p1 is 1 or more, and when q1 is 3 or more, M 1 represents a p1+q1 valent group, and a plurality of R 1 s and L 1 s may be the same or different.) [C4] (In formula 2, L 2 represents a polymer chain, the polymer chain including all of a repeating unit consisting of an oxyalkylenecarbonyl group, a repeating unit derived from D-lactic acid, and a repeating unit derived from L-lactic acid; X 2 represents a group having the same curable group as X 1 in formula 1; R 2 represents a hydrogen atom or a monovalent substituent not having the curable group; q2 represents an integer of 2 or more; p2 represents an integer of 0 or more; when q2 is 2 and p2 is 0, M 2 represents a single bond or a divalent group; when q2 is 2 and p2 is 1 or more, and when q2 is 3 or more, M 2 represents a p2+q divalent group; and a plurality of R 2 s and L 2 s may be the same or different.)

6. The method according to claim 5 , wherein the application of energy is carried out by heating the compact.

7. The method of claim 5 , wherein the application of energy is carried out under pressure.

Citation Information

Patent Citations

  • Tri-shape shape memory conductive polymeric nanocomposite and preparation method thereof

    CN106566398A

  • Shape memory-based multi-stimulated sensing conductive polymer material and preparation method and application thereof

    CN106674998A

  • Adjustable strain-sensing high polymer with hybridized nano conducting material

    CN106883586A

  • Surface acoustic wave-based shape memory composite member controllable deformation three-dimensional printing method

    CN111572019A

  • Thermoplastic shape memory resin sheet and article including thermoplastic shape memory resin sheet

    JP2021023499A